Composition containing cellulose nanofibers
Patent Information
- Application Number
- JP2023182623
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-02
- Filing Date
- 2023-10-24
- Publication Date
- 2025-02-12
AI Technical Summary
Cellulose nanofibers, being inherently hydrophilic, face challenges in uniform dispersion within hydrophobic rubber due to poor affinity, limiting their use in rubber molded articles that require high mechanical strength, flexibility, and abrasion resistance.
A rubber composition comprising cellulose nanofibers, a liquid rubber component, and a surfactant, particularly nonionic surfactants, is formulated to enhance dispersion, ensuring well-dispersed cellulose nanofibers in rubber, thereby improving elastic modulus and abrasion resistance.
The composition enables the formation of rubber products with excellent mechanical properties, including elastic modulus and abrasion resistance, by effectively dispersing cellulose nanofibers within the rubber matrix.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] One aspect of the present disclosure relates to a composition containing cellulose nanofibers. [Background technology]
[0002] Conventionally, rubber molded articles are required to have a high degree of balance among various properties such as mechanical strength, flexibility, abrasion resistance, and processability, and for example, fillers are generally contained in the rubber molded articles for the purpose of improving elastic modulus, hardness, abrasion resistance, etc. In order for such filler-containing rubber molded articles to exhibit the desired properties, it is important that the filler is well dispersed in the rubber.
[0003] For example, Patent Document 1 describes a rubber composition for tires that is characterized by blending oxidized cellulose nanofibers with diene rubber, including modified diene rubber, for the purpose of improving mechanical properties. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-147877 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, due to the growing awareness of environmental issues, various methods have been explored for using cellulose, a low specific gravity and renewable material, as a filler to be contained in rubber molded bodies. Among them, cellulose nanofibers are extremely promising as a filler for polymer molded bodies because the reinforcing effect per amount used is good when the polymer molded body is formed by combining it with various polymers. If such cellulose nanofibers can be used in rubber molded bodies, it is possible to provide rubber molded bodies that have low specific gravity and excellent physical properties, can be used for various applications, and are advantageous in terms of transportation costs and disposal costs. However, since cellulose nanofibers are essentially hydrophilic due to the contribution of hydroxyl groups in cellulose, it is generally difficult to mix them with rubber, which is a highly hydrophobic material. Patent Document 1 describes a rubber composition for tires in which oxidized cellulose nanofibers, which are a filler, are dispersed in a diene rubber containing a modified diene rubber. However, this technology is a technology that improves dispersibility by improving the affinity of the oxidized cellulose nanofibers to the diene rubber with the modified diene rubber. Even if the cellulose nanofibers do not have ionic groups, a rubber molded article in which the cellulose nanofibers are well dispersed in the rubber has not yet been provided.
[0006] One aspect of the present invention aims to solve the above problems and provide a rubber composition in which cellulose nanofibers are well dispersed in the rubber, making it possible to form a molded article having excellent elastic modulus, abrasion resistance, etc. [Means for solving the problem]
[0007] The present disclosure encompasses the following aspects. [1] A rubber composition comprising cellulose nanofibers, a first rubber component which is a liquid rubber, and a surfactant. [2] The rubber composition according to claim 1, wherein the cellulose nanofibers have no ionic groups. [3] The rubber composition according to the above embodiment 1 or 2, wherein the liquid rubber has a number average molecular weight of 1,000 to 80,000. [4] The rubber composition according to any one of the above aspects 1 to 3, wherein the ratio (Mw / Mn) of the number average molecular weight (Mn) to the weight average molecular weight (Mw) of the liquid rubber is 1.5 to 5. [5] The rubber composition according to any one of the above embodiments 1 to 4, wherein the liquid rubber has a viscosity of 1,000,000 mPa·s or less at 80° C. [6] The rubber composition according to any one of the above aspects 1 to 5, wherein the liquid rubber has a viscosity of 1,000,000 mPa·s or less at 25° C. [7] The rubber composition according to any one of the above embodiments 1 to 6, wherein the liquid rubber has a viscosity of 1,000,000 mPa·s or less at 0° C. [8] The rubber composition according to any one of the above aspects 1 to 7, wherein the liquid rubber comprises at least one selected from the group consisting of diene rubber, silicone rubber, urethane rubber, polysulfide rubber, and hydrogenated products thereof. [9] The rubber composition according to any one of the above aspects 1 to 8, wherein the cellulose nanofiber has a degree of substitution of 0.
[10] The rubber composition according to any one of the above aspects 1 to 9, comprising 0.5% by mass to 10% by mass of the cellulose nanofibers.
[11] The rubber composition according to any one of the above aspects 1 to 10, wherein the surfactant is contained in an amount of 10 parts by mass to 200 parts by mass per 100 parts by mass of the cellulose nanofibers.
[12] The rubber composition according to any one of the above embodiments 1 to 11, wherein the surfactant is a nonionic surfactant or a cationic surfactant.
[13] The rubber composition according to claim 12, wherein the surfactant is a nonionic surfactant.
[14] The rubber composition according to claim 13, wherein the nonionic surfactant is a compound having a hydrophilic group selected from the group consisting of a hydroxyl group, a carboxyl group, a sulfonic acid group, and an amino group, and a hydrocarbon group.
[15] The nonionic surfactant is represented by the following general formula (1): R-(OCH2CH2) m -OH (1) [wherein R represents a monovalent aliphatic group having 6 to 30 carbon atoms, and m is a natural number smaller than the number of carbon atoms in R], and The following general formula (2): R1OCH2-(CHOH)4-CH2OR2(2) [wherein R1 and R2 each independently represent a hydrogen atom, an aliphatic group having 1 to 30 carbon atoms, -COR3 {wherein R3 represents an aliphatic group having 1 to 30 carbon atoms}, or -(CH2CH2O) y -R4 {wherein R4 represents a hydrogen atom or an aliphatic group having 1 to 30 carbon atoms, and y represents an integer of 1 to 30.}, 15. The rubber composition according to claim 13 or 14, wherein the rubber composition is one or more selected from the group consisting of:
[16] The rubber composition according to any one of the above embodiments 1 to 15, wherein at least a portion of the surface of the cellulose nanofiber is covered with the first rubber component.
[17] A powder comprising the rubber composition according to any one of the first to sixteenth aspects.
[18] Compacted bulk density of 0.01 g / cm 3 ~0.30g / cm 3 18. The powder according to claim 17, wherein
[19] A masterbatch, which is a mixture of the powder according to aspect 17 or 18 and a second rubber component.
[20] A method for producing a masterbatch, comprising the step of kneading the powder according to aspect 17 or 18 with a second rubber component to obtain a masterbatch.
[21] A rubber composite, comprising a mixture of the powder according to aspect 17 or 18 or the masterbatch according to aspect 19 and a third rubber component.
[22] The rubber composite of claim 21, wherein at least a portion of the surface of the cellulose nanofiber is covered with the first rubber component.
[23] Kneading the powder according to the above embodiment 17 or 18 with a third rubber component; or Forming a masterbatch by the method according to aspect 20, and then kneading the masterbatch with a third rubber component; A method for producing a rubber composite, comprising the step of obtaining a rubber composite by
[24] The method described in claim 23, wherein in the rubber composite, at least a portion of the surface of the cellulose nanofiber is covered with the first rubber component.
[25] A cured rubber product, which is a cured product of the rubber composite according to any one of claims 21 to 22.
[26] Obtaining a rubber composite by the method according to aspect 23 or 24; and A step of curing the rubber composite to obtain a cured rubber product. The method for producing a cured rubber product comprising the steps of:
[27] A shoe outsole comprising the rubber vulcanized product according to embodiment 25.
[28] A tire comprising the rubber vulcanized product according to embodiment 25.
[29] A vibration-isolating rubber comprising the cured rubber material according to aspect 25.
[30] A power transmission belt comprising the cured rubber according to embodiment 25. Effect of the Invention
[0008] According to one aspect of the present invention, a rubber composition can be provided in which cellulose nanofibers are well dispersed in rubber, making it possible to form a molded article having excellent elastic modulus, abrasion resistance, and the like. [Brief description of the drawings]
[0009] [Figure 1] FIG. 13 is a view showing a scanning electron microscope image of a cross section of the powder obtained in Example 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, exemplary embodiments of the present invention (hereinafter, abbreviated as "present embodiments") will be described, but the present invention is not limited to these embodiments. Note that, unless otherwise specified, the characteristic values of the present disclosure are values measured by the method described in the [Examples] section of the present disclosure or a method that is understood to be equivalent to the above by a person skilled in the art.
[0011] <Rubber composition> One aspect of the present disclosure provides a rubber composition comprising cellulose nanofibers, a surfactant, and a first rubber component that is a liquid rubber. Cellulose nanofibers are essentially hydrophilic due to their hydroxyl groups, while rubber is essentially hydrophobic, and it is usually difficult to uniformly disperse cellulose nanofibers in rubber. For example, the dispersibility can be improved to a certain extent by using a dispersant, but from the viewpoint of preventing deterioration of the physical properties of a molded body, it is desirable to uniformly disperse cellulose nanofibers in rubber while minimizing the need for additives. As a result of various studies from this perspective, the present inventors have found that a rubber composition can be prepared by dispersing cellulose nanofibers in a specific rubber that has fluidity at a predetermined temperature, and then kneading the rubber composition with rubber, for example in the form of a rubber master batch, to produce a rubber composite, thereby forming a cured rubber product that does not impair the inherent physical properties of the rubber and in which the reinforcing effect of the cellulose nanofibers is well expressed. According to the rubber composition of this embodiment, the cellulose nanofibers are well dispersed in the rubber, making it possible to form a cured rubber product with good properties (particularly elastic modulus, hardness, etc.), and such cured rubber product can form a molded article with excellent elastic modulus, abrasion resistance, etc., because the cellulose nanofibers are well dispersed in the rubber. Preferred examples of each component of the rubber composition of the present embodiment will now be described.
[0012] <Cellulose nanofiber> As raw materials for cellulose nanofibers, natural cellulose and regenerated cellulose can be used. As natural cellulose, wood pulp obtained from wood species (broadleaf or coniferous trees), non-wood pulp obtained from non-wood species (cotton, bamboo, hemp, bagasse, kenaf, cotton linters, sisal, straw, etc.), and cellulose aggregates produced by animals (e.g., ascidians), algae, and microorganisms (e.g., acetic acid bacteria) can be used. As regenerated cellulose, regenerated cellulose fibers (viscose, cupra, tencel, etc.), cellulose derivative fibers, and ultrafine threads of regenerated cellulose or cellulose derivatives obtained by electrospinning can be used.
[0013] In one embodiment, the cellulose nanofiber is a fine cellulose fiber obtained by treating pulp or the like with hot water of 100°C or higher, hydrolyzing and weakening hemicellulose, and then mechanically defibrating the cellulose nanofiber by a pulverizing method such as a high-pressure homogenizer, a microfluidizer, a ball mill, a disk mill, or a mixer (e.g., a homomixer). In one embodiment, the cellulose nanofiber has a number average fiber diameter of 1 nm or more and 1000 nm or less. The cellulose nanofiber may be chemically modified as described below, but in terms of the reinforcing effect as a filler, it is preferable to use a non-chemically modified cellulose nanofiber. For example, cellulose nanofibers defibrated by chemical oxidation treatment such as 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) phosphate ester tend to have low heat resistance due to the ionic group (e.g., carboxyl group) introduced into the cellulose nanofiber, and also tend to have a small fiber diameter after defibration. In terms of the reinforcing effect as a filler, cellulose nanofibers that are only mechanically defibrated (i.e., not chemically defibrated such as oxidation) are more advantageous. Therefore, in a preferred embodiment, the cellulose nanofibers have no ionic groups. In this disclosure, the cellulose nanofibers have no ionic groups means that the amount of ionic groups measured by conductometric titration is 0.1 mmol / g or less.
[0014] The slurry can be prepared by dispersing the cellulose fibers in a liquid medium, and the dispersion may be carried out using a high-pressure homogenizer, a microfluidizer, a ball mill, a disk mill, a mixer (e.g., a homomixer), etc., and the product of the defibration may be obtained as the product of the slurry preparation process of the present disclosure. The liquid medium in the slurry may further contain, in addition to water, other liquid media (e.g., organic solvents) either alone or in combination of two or more. Examples of the organic solvent include commonly used water-miscible organic solvents, such as alcohols having a boiling point of 50° C. to 170° C. (e.g., methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, s-butanol, t-butanol, etc.); ethers (e.g., propylene glycol monomethyl ether, 1,2-dimethoxyethane, diisopropyl ether, tetrahydrofuran, 1,4-dioxane, etc.); carboxylic acids (e.g., formic acid, acetic acid, lactic acid, etc.); esters (e.g., ethyl acetate, vinyl acetate, etc.); ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, etc.); and nitrogen-containing solvents (dimethylformamide, dimethylacetamide, acetonitrile, etc.). In a typical embodiment, the liquid medium in the slurry is substantially water alone.
[0015] Since the cellulose raw material contains alkali soluble matter and sulfuric acid insoluble matter (lignin, etc.), the alkali soluble matter and sulfuric acid insoluble matter may be reduced through a purification process such as delignification by cooking and a bleaching process. On the other hand, the purification process such as delignification by cooking and the bleaching process cut the molecular chains of cellulose, changing the weight average molecular weight and number average molecular weight, so it is desirable to control the purification process and bleaching process of the cellulose raw material so that the weight average molecular weight of the cellulose nanofiber and the ratio of the weight average molecular weight to the number average molecular weight are within an appropriate range.
[0016] In addition, since the refining process such as delignification by cooking and the bleaching process reduce the molecular weight of cellulose molecules, there is concern that these processes will result in a lower molecular weight of cellulose nanofibers and alter the cellulose raw material, increasing the proportion of alkali-soluble matter. Since alkali-soluble matter has poor heat resistance, it is desirable to control the refining process and bleaching process of the cellulose raw material so that the amount of alkali-soluble matter contained in the cellulose raw material is within a certain range or less.
[0017] In one aspect, the number average fiber diameter of the cellulose nanofibers is preferably 2 to 1000 nm from the viewpoint of obtaining a good effect of improving physical properties by the cellulose nanofibers. The number average fiber diameter of the cellulose nanofibers is more preferably 4 nm or more, or 5 nm or more, or 10 nm or more, or 15 nm or more, or 20 nm or more, and more preferably 500 nm or less, or 450 nm or less, or 400 nm or less, or 350 nm or less, or 300 nm or less, or 250 nm or less.
[0018] From the viewpoint of satisfactorily improving the mechanical properties of a rubber composite containing cellulose nanofibers with a small amount of cellulose nanofibers, the average fiber length (L) / fiber diameter (D) ratio of the cellulose nanofibers is preferably 30 or more, or 50 or more, or 80 or more, or 100 or more, or 120 or more, or 150 or more. There is no particular upper limit, but from the viewpoint of handleability, it is preferably 5,000 or less.
[0019] In the present disclosure, the fiber length, fiber diameter, and L / D ratio of the cellulose nanofibers are determined by dispersing an aqueous dispersion of cellulose nanofibers using a high-shear homogenizer (e.g., Nippon Seiki Co., Ltd., product name "Excel Auto Homogenizer ED-7") under processing conditions: rotation speed 15,000 rpm × 5 minutes, diluting the aqueous dispersion with pure water to 0.1 to 0.5 mass%, casting it on mica, and air-drying it to obtain a measurement sample, and measuring it with a scanning electron microscope (SEM) or atomic force microscope (AFM). Specifically, the length (L) and diameter (D) of 100 randomly selected cellulose nanofibers are measured in an observation field where the magnification is adjusted so that at least 100 cellulose nanofibers are observed, and the ratio (L / D) is calculated. The number average value of the fiber length (L), the number average value of the fiber diameter (D), and the number average value of the ratio (L / D) are calculated for the cellulose nanofibers.
[0020] Alternatively, the fiber length, fiber diameter, and L / D ratio of the cellulose nanofiber contained in the powder, rubber composition, rubber masterbatch, rubber composite, etc. can be confirmed by measuring these as measurement samples using the above-mentioned measurement method.
[0021] Alternatively, the fiber length, fiber diameter, and L / D ratio of cellulose nanofibers contained in powders, rubber compositions, rubber masterbatches, rubber composites, etc. can be confirmed by dissolving the polymer components contained therein in an organic or inorganic solvent capable of dissolving the polymer components, isolating the cellulose nanofibers, thoroughly washing with the solvent, and then replacing the solvent with pure water to prepare an aqueous dispersion, diluting the cellulose nanofiber concentration with pure water to 0.1 to 0.5% by mass, casting on mica, and air-drying the resulting sample, which is then used as a measurement sample and measured using the above-mentioned measurement method. At this time, the measurement is performed on 100 or more randomly selected cellulose nanofibers.
[0022] The crystallinity of the cellulose nanofiber is preferably 55% or more. When the crystallinity is in this range, the mechanical properties (strength, dimensional stability) of the cellulose itself are high, so that when the cellulose nanofiber is dispersed in rubber, the strength and dimensional stability of the rubber composite tend to be high. A more preferable lower limit of the crystallinity is 60%, even more preferably 70%, and most preferably 80%. There is no particular upper limit for the crystallinity of the cellulose nanofiber, and the higher the better, but from the viewpoint of production, a preferable upper limit is 99%.
[0023] Alkali-soluble polysaccharides such as hemicellulose and acid-insoluble components such as lignin are present between the microfibrils and between the microfibril bundles of plant-derived cellulose nanofibers. Hemicellulose is a polysaccharide composed of sugars such as mannan and xylan, and plays a role in binding the microfibrils together by hydrogen bonding with cellulose. Lignin is also a compound having an aromatic ring, and is known to be covalently bonded to hemicellulose in the cell walls of plants. If there is a large amount of impurities such as lignin remaining in the cellulose nanofibers, discoloration may occur due to heat during processing. Therefore, from the viewpoint of suppressing discoloration of the rubber composite during extrusion processing and molding processing, it is desirable to set the crystallinity of the cellulose nanofibers within the above-mentioned range.
[0024] The degree of crystallinity here, when the cellulose is cellulose type I crystal (derived from natural cellulose), is calculated from the diffraction pattern (2θ / deg. is 10 to 30) obtained by measuring a sample by wide-angle X-ray diffraction using the Segal method, according to the following formula: Crystallinity (%) = ([diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] - [diffraction intensity due to amorphous matter at 2θ / deg. = 18]) / [diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] × 100
[0025] When the cellulose is cellulose II type crystal (derived from regenerated cellulose), the degree of crystallinity can be calculated from the absolute peak intensity h0 at 2θ=12.6° assigned to the (110) plane peak of cellulose II type crystal in wide-angle X-ray diffraction and the peak intensity h1 from the baseline at this interplanar spacing, according to the following formula: Crystallinity (%) =h1 / h0 ×100
[0026] Known cellulose crystal forms include type I, type II, type III, and type IV, of which types I and II are particularly widely used, and types III and IV have been obtained on a laboratory scale but are not widely used on an industrial scale. The cellulose nanofibers of the present disclosure are preferably cellulose nanofibers containing cellulose type I crystals or cellulose type II crystals, since they have relatively high structural mobility and, by dispersing the cellulose nanofibers in rubber, can provide molded articles with a lower linear expansion coefficient and superior strength and elongation during tensile and bending deformation, and more preferably cellulose nanofibers containing cellulose type I crystals and having a crystallinity of 55% or more.
[0027] In addition, the degree of polymerization of the cellulose nanofiber is preferably 100 or more, more preferably 150 or more, more preferably 200 or more, more preferably 300 or more, more preferably 400 or more, more preferably 450 or more, and preferably 3500 or less, more preferably 3300 or less, more preferably 3200 or less, more preferably 3100 or less, and more preferably 3000 or less.
[0028] From the viewpoint of processability and mechanical property expression, it is desirable that the degree of polymerization of the cellulose nanofiber is within the above-mentioned range. From the viewpoint of processability, it is preferable that the degree of polymerization is not too high, and from the viewpoint of mechanical property expression, it is desirable that the degree of polymerization is not too low.
[0029] The degree of polymerization of cellulose nanofibers refers to the average degree of polymerization measured according to the reduced specific viscosity method using a copper ethylenediamine solution described in the Verification Test (3) of the "15th Revised Japanese Pharmacopoeia Commentary (published by Hirokawa Shoten)."
[0030] In one embodiment, the weight average molecular weight (Mw) of the cellulose nanofiber is 100,000 or more, more preferably 200,000 or more. The ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) is 6 or less, preferably 5.4 or less. The larger the weight average molecular weight, the fewer the number of terminal groups of the cellulose molecule. In addition, since the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight represents the width of the molecular weight distribution, the smaller the Mw / Mn, the fewer the number of terminals of the cellulose molecule. Since the terminals of the cellulose molecules are the starting points of thermal decomposition, when the cellulose molecules of the cellulose nanofibers not only have a large weight average molecular weight but also have a narrow molecular weight distribution, a cellulose nanofiber with particularly high heat resistance and a rubber composition containing the cellulose nanofiber and rubber can be obtained. The weight average molecular weight (Mw) of the cellulose nanofiber may be, for example, 600,000 or less, or 500,000 or less, from the viewpoint of the availability of the cellulose raw material. From the viewpoint of ease of production of cellulose nanofibers, the ratio (Mw / Mn) of weight average molecular weight to number average molecular weight (Mn) may be, for example, 1.5 or more, or 2 or more. Mw can be controlled to the above range by selecting a cellulose raw material having an Mw appropriate for the purpose, by appropriately performing physical and / or chemical treatment on the cellulose raw material within an appropriate range, etc. Mw / Mn can also be controlled to the above range by selecting a cellulose raw material having an Mw / Mn appropriate for the purpose, by appropriately performing physical and / or chemical treatment on the cellulose raw material within an appropriate range, etc. Each of the Mw and Mw / Mn of the cellulose raw material may be within the above range in one embodiment. In both the control of Mw and the control of Mw / Mn, examples of the physical treatment include dry or wet grinding using a microfluidizer, ball mill, disk mill, or the like, and physical treatments that apply mechanical forces such as impact, shear, friction, and the like using a crusher, homomixer, high-pressure homogenizer, ultrasonic device, or the like, and examples of the chemical treatment include digestion, bleaching, acid treatment, and conversion to regenerated cellulose.
[0031] The weight average molecular weight and number average molecular weight of the cellulose nanofiber referred to here are values obtained by dissolving the cellulose nanofiber in N,N-dimethylacetamide containing added lithium chloride and then performing gel permeation chromatography using N,N-dimethylacetamide as a solvent.
[0032] Methods for controlling the degree of polymerization (i.e., average degree of polymerization) or molecular weight of cellulose nanofibers include hydrolysis. Hydrolysis promotes depolymerization of amorphous cellulose inside the cellulose nanofibers, decreasing the average degree of polymerization. At the same time, hydrolysis removes impurities such as hemicellulose and lignin in addition to the above-mentioned amorphous cellulose, making the inside of the fiber more porous.
[0033] The hydrolysis method is not particularly limited, and examples thereof include acid hydrolysis, alkali hydrolysis, hydrothermal decomposition, steam explosion, and microwave decomposition. These methods may be used alone or in combination of two or more. In the acid hydrolysis method, for example, α-cellulose obtained as pulp from a fibrous plant is used as a cellulose raw material, and this is dispersed in an aqueous medium, and an appropriate amount of a protonic acid, a carboxylic acid, a Lewis acid, a heteropoly acid, etc. is added, and the mixture is heated while stirring, so that the average degree of polymerization can be easily controlled. The reaction conditions such as temperature, pressure, and time at this time vary depending on the cellulose type, cellulose concentration, acid type, acid concentration, etc., but are appropriately adjusted so that the desired average degree of polymerization is achieved. For example, a condition in which a mineral acid aqueous solution of 2% by mass or less is used and cellulose nanofibers are treated at 100°C or higher under pressure for 10 minutes or more can be mentioned. Under these conditions, the catalyst component such as acid penetrates into the inside of the cellulose nanofibers, promoting hydrolysis, reducing the amount of catalyst component used, and making subsequent purification easier. The dispersion of the cellulose raw material during hydrolysis may contain, in addition to water, a small amount of an organic solvent within a range that does not impair the effects of the present invention.
[0034] Alkali-soluble polysaccharides that may be contained in cellulose nanofibers include hemicellulose, β-cellulose, and γ-cellulose. Alkali-soluble polysaccharides are understood by those skilled in the art as components obtained as the alkali-soluble portion of holocellulose obtained by solvent extraction and chlorine treatment of plants (e.g., wood) (i.e., components obtained by removing α-cellulose from holocellulose). Alkali-soluble polysaccharides are polysaccharides containing hydroxyl groups and have poor heat resistance, and may cause inconveniences such as decomposition when exposed to heat, yellowing during thermal aging, and a decrease in strength of cellulose nanofibers. Therefore, it is preferable that the content of alkali-soluble polysaccharides in cellulose nanofibers is low.
[0035] In one aspect, the average content of alkali-soluble polysaccharides in the cellulose nanofibers is preferably 20% by mass or less, 18% by mass or less, 15% by mass or less, or 12% by mass or less, relative to 100% by mass of the cellulose nanofibers, from the viewpoint of obtaining good dispersibility of the cellulose nanofibers. From the viewpoint of ease of production of the cellulose nanofibers, the above content may be 1% by mass or more, 2% by mass or more, or 3% by mass or more.
[0036] The average alkali-soluble polysaccharide content can be determined by the method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000), by subtracting the α-cellulose content from the holocellulose content (Wise method). This method is understood in the industry as a method for measuring the amount of hemicellulose. The alkali-soluble polysaccharide content is calculated three times for each sample, and the number average of the calculated alkali-soluble polysaccharide contents is taken as the average alkali-soluble polysaccharide content.
[0037] In one aspect, the average content of acid-insoluble components in the cellulose nanofibers is preferably 10% by mass or less, 5% by mass or less, or 3% by mass or less, relative to 100% by mass of the cellulose nanofibers, from the viewpoint of avoiding a decrease in heat resistance of the cellulose nanofibers and the associated discoloration. From the viewpoint of ease of production of the cellulose nanofibers, the above content may be 0.1% by mass or more, 0.2% by mass or more, or 0.3% by mass or more.
[0038] The average acid-insoluble content is determined as a quantitative determination of the acid-insoluble content using the Clason method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000). This method is understood in the industry as a method for measuring the amount of lignin. The sample is stirred in a sulfuric acid solution to dissolve cellulose, hemicellulose, etc., and then filtered through a glass fiber filter paper, and the resulting residue corresponds to the acid-insoluble content. The acid-insoluble content is calculated from the weight of the acid-insoluble content, and the number average of the acid-insoluble content calculated for the three samples is taken as the average acid-insoluble content.
[0039] The thermal decomposition temperature of cellulose nanofiber (T D ) is 270° C. or higher in one embodiment, from the viewpoint of being able to exhibit the heat resistance and mechanical strength desired for in-vehicle applications and the like, preferably 275° C. or higher, more preferably 280° C. or higher, and even more preferably 285° C. or higher. The higher the thermal decomposition onset temperature, the more preferable it is, but from the viewpoint of ease of production of cellulose nanofibers, it may be, for example, 320° C. or lower, or 300° C. or lower.
[0040] In this disclosure, T D is a value obtained from a graph in which the horizontal axis is temperature and the vertical axis is the weight residual rate % in thermogravimetry (TG) analysis. Starting from the weight of cellulose nanofiber at 150°C (a state in which most of the moisture has been removed) (weight loss of 0 wt%), the temperature is continued to be increased until the temperature at which the weight loss reaches 1 wt% (T 1% ) and the temperature at which the weight loss reaches 2 wt% (T 2%The temperature at the point where this line intersects with the horizontal line (baseline) that passes through the starting point of the weight loss of 0 wt% is called T D It is defined as:
[0041] 1% weight loss temperature (T 1% ) is the above T D This is the temperature at which the weight loss reaches 1% by weight, starting from the weight at 150°C, when the temperature is continued to be increased using the method described above.
[0042] Weight loss rate of cellulose nanofiber at 250°C (T 250℃ ) is the weight loss rate when cellulose nanofibers were kept at 250°C under nitrogen flow for 2 hours in TG analysis.
[0043] (chemical modification) The cellulose nanofibers may be chemically modified cellulose nanofibers. The cellulose nanofibers may be chemically modified in advance, for example, at the stage of raw pulp or linters, during or after the defibration treatment, or during or after the slurry preparation process, or during or after the drying (granulation) process.
[0044] As a modifying agent for cellulose nanofibers, a compound that reacts with the hydroxyl groups of cellulose can be used, and examples of such agents include esterifying agents, etherifying agents, and silylation agents. On the other hand, modifying agents having polar groups, such as carboxylic acids and phosphoric esters, tend to reduce the heat resistance of cellulose nanofibers by introducing ionic groups (e.g., carboxyl groups) into the cellulose nanofibers, and also tend to reduce the fiber diameter after defibration, so it is preferable not to use them from the viewpoint of the reinforcing effect as a filler. In a preferred embodiment, the chemical modification is acylation using an esterifying agent, and acetylation is particularly preferred. As the esterifying agent, acid halides, acid anhydrides, vinyl carboxylates, and carboxylic acids are preferred.
[0045] The acid halide may be at least one selected from the group consisting of compounds represented by the following formula: R 1-C(=O)-X (In the formula, R 1 represents an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 24 carbon atoms, or an aryl group having 6 to 24 carbon atoms, and X is Cl, Br, or I. Specific examples of acid halides include, but are not limited to, acetyl chloride, acetyl bromide, acetyl iodide, propionyl chloride, propionyl bromide, propionyl iodide, butyryl chloride, butyryl bromide, butyryl iodide, benzoyl chloride, benzoyl bromide, and benzoyl iodide. Among them, acid chlorides can be preferably used in terms of reactivity and handling. In addition, in the reaction of acid halides, one or more alkaline compounds may be added to act as a catalyst and neutralize the by-product acidic substances. Specific examples of alkaline compounds include, but are not limited to, tertiary amine compounds such as triethylamine and trimethylamine; and nitrogen-containing aromatic compounds such as pyridine and dimethylaminopyridine.
[0046] As the acid anhydride, any suitable acid anhydride can be used. For example, Anhydrides of saturated aliphatic monocarboxylic acids such as acetic acid, propionic acid, (iso)butyric acid, valeric acid, etc.; anhydrides of unsaturated aliphatic monocarboxylic acids such as (meth)acrylic acid, oleic acid, etc.; Anhydrides of alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid and tetrahydrobenzoic acid; Anhydrides of aromatic monocarboxylic acids such as benzoic acid, 4-methylbenzoic acid, etc.; Examples of dibasic carboxylic acid anhydrides include anhydrides of saturated aliphatic dicarboxylic acids such as succinic acid and adipic acid; unsaturated aliphatic dicarboxylic acid anhydrides such as maleic anhydride and itaconic anhydride; alicyclic dicarboxylic acid anhydrides such as 1-cyclohexene-1,2-dicarboxylic acid anhydride, hexahydrophthalic anhydride, and methyltetrahydrophthalic anhydride; and aromatic dicarboxylic acid anhydrides such as phthalic anhydride and naphthalic anhydride. Examples of polybasic carboxylic acid anhydrides having three or more bases include polycarboxylic acids (anhydrides) such as trimellitic anhydride and pyromellitic anhydride. In addition, in the reaction of an acid anhydride, one or more types of acidic compounds such as sulfuric acid, hydrochloric acid, phosphoric acid, etc., or Lewis acids (for example, Lewis acid compounds represented by MYn, where M represents a semimetal element such as B, As, Ge, etc., or a base metal element such as Al, Bi, In, etc., or a transition metal element such as Ti, Zn, Cu, etc., or a lanthanoid element, n is an integer corresponding to the atomic valence of M and represents 2 or 3, and Y represents a halogen atom, OAc, OCOCF3, ClO4, SbF6, PF6, or OSO2CF3(OTf)), or alkaline compounds such as triethylamine, pyridine, etc. may be added as a catalyst.
[0047] The vinyl carboxylate may be represented by the following formula: R-COO-CH=CH2 {wherein R is any one of an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 16 carbon atoms, and an aryl group having 6 to 24 carbon atoms.} is preferred. The vinyl carboxylate is more preferably at least one selected from the group consisting of vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl cyclohexanecarboxylate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, vinyl octylate, divinyl adipate, vinyl methacrylate, vinyl crotonate, vinyl octylate, vinyl benzoate, and vinyl cinnamate. In the esterification reaction with a vinyl carboxylate, one or more catalysts selected from the group consisting of alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkaline earth metal carbonates, alkali metal hydrogencarbonates, primary to tertiary amines, quaternary ammonium salts, imidazole and derivatives thereof, pyridine and derivatives thereof, and alkoxides may be added.
[0048] Examples of the alkali metal hydroxides and alkaline earth metal hydroxides include sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, barium hydroxide, etc. Examples of the alkali metal carbonates, alkaline earth metal carbonates, and alkali metal hydrogen carbonates include lithium carbonate, sodium carbonate, potassium carbonate, cesium carbonate, magnesium carbonate, calcium carbonate, barium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, cesium hydrogen carbonate, etc.
[0049] The primary, secondary and tertiary amines refer to primary, secondary and tertiary amines, and specific examples thereof include ethylenediamine, diethylamine, proline, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethyl-1,3-propanediamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, tris(3-dimethylaminopropyl)amine, N,N-dimethylcyclohexylamine and triethylamine.
[0050] Examples of imidazole and its derivatives include 1-methylimidazole, 3-aminopropylimidazole, and carbonyldiimidazole.
[0051] Examples of pyridine and its derivatives include N,N-dimethyl-4-aminopyridine and picoline.
[0052] Examples of the alkoxide include sodium methoxide, sodium ethoxide, and potassium t-butoxide.
[0053] The carboxylic acid may be at least one selected from the group consisting of compounds represented by the following formulas: R-COOH (In the formula, R represents an alkyl group having 1 to 16 carbon atoms, an alkenyl group having 2 to 16 carbon atoms, a cycloalkyl group having 3 to 16 carbon atoms, or an aryl group having 6 to 16 carbon atoms.)
[0054] Specific examples of carboxylic acids include at least one selected from the group consisting of acetic acid, propionic acid, butyric acid, caproic acid, cyclohexane carboxylic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, pivalic acid, methacrylic acid, crotonic acid, octylic acid, benzoic acid, and cinnamic acid.
[0055] Among these carboxylic acids, at least one selected from the group consisting of acetic acid, propionic acid, and butyric acid, and particularly acetic acid, is preferred from the viewpoint of reaction efficiency. In addition, in the reaction of carboxylic acid, one or more types of acidic compounds such as sulfuric acid, hydrochloric acid, phosphoric acid, etc., or Lewis acids (for example, Lewis acid compounds represented by MYn, where M represents a semimetal element such as B, As, Ge, etc., or a base metal element such as Al, Bi, In, etc., or a transition metal element such as Ti, Zn, Cu, etc., or a lanthanoid element, n is an integer corresponding to the atomic valence of M and represents 2 or 3, and Y represents a halogen atom, OAc, OCOCF3, ClO4, SbF6, PF6, or OSO2CF3(OTf)), or alkaline compounds such as triethylamine, pyridine, etc. may be added as a catalyst.
[0056] Among these esterification reactants, at least one selected from the group consisting of acetic anhydride, propionic anhydride, butyric anhydride, vinyl acetate, vinyl propionate, vinyl butyrate, and acetic acid, and among these, acetic anhydride and vinyl acetate are preferred from the viewpoint of reaction efficiency.
[0057] When cellulose nanofibers are chemically modified (e.g., by hydrophobization such as acylation), the cellulose nanofibers tend to have good dispersibility in rubber, but the cellulose nanofibers of the present disclosure can exhibit good dispersibility in rubber even if they are unsubstituted or have a low degree of substitution.
[0058] In one embodiment, the degree of substitution of the cellulose nanofibers is 0 (i.e., unsubstituted). Alternatively, in one embodiment, from the viewpoint of obtaining chemically modified cellulose nanofibers with a high thermal decomposition onset temperature, the degree of acyl substitution (DS) of the cellulose nanofibers may be greater than 0, or 0.1 or more, or 0.2 or more, or 0.25 or more, or 0.3 or more, or 0.5 or more. In addition, since an unmodified cellulose skeleton remains in the esterified cellulose nanofibers, it is possible to obtain esterified cellulose nanofibers that combine high tensile strength and dimensional stability derived from cellulose with a high thermal decomposition onset temperature derived from chemical modification, the degree of acyl substitution (DS) of the cellulose nanofibers may be 1.2 or less, or 1.0 or less, or 0.8 or less, or 0.7 or less, or 0.6 or less, or 0.5 or less.
[0059] When the modification group of the chemically modified cellulose nanofiber is an acyl group, the degree of acyl substitution (DS) can be calculated based on the peak intensity ratio of the peak derived from the acyl group to the peak derived from the cellulose skeleton from the attenuated total reflectance (ATR) infrared absorption spectrum of the esterified cellulose nanofiber. The peak of the absorption band of C=O based on the acyl group is at 1730 cm -1 The absorption band of CO based on the cellulose backbone appears at 1030 cm -1 The DS of esterified cellulose nanofibers was calculated by plotting a correlation graph between the DS obtained from solid-state NMR measurements of esterified cellulose nanofibers (described below) and the modification ratio (IR index 1030), which is defined as the ratio of the peak intensity of the absorption band of C=O based on acyl groups to the peak intensity of the absorption band of CO in the cellulose backbone chain, and then calculating the calibration curve from the correlation graph. Degree of substitution DS = 4.13 × IR index (1030) It can be found by using
[0060] From the viewpoint of obtaining a good reinforcing effect of the cellulose nanofibers, the content of cellulose nanofibers in the rubber composition is preferably 0.5% by mass or more, or 1% by mass or more, or 3% by mass or more, and from the viewpoint of obtaining a rubber molded body having good rubber elasticity, the content of cellulose nanofibers is preferably 80% by mass or less, or 60% by mass or less, or 33% by mass or less, or 30% by mass or less, or 20% by mass or less, or 10% by mass or less.
[0061] <First rubber component (liquid rubber)> In the present disclosure, liquid rubber means a substance that has fluidity at 23°C and forms a rubber elastomer by crosslinking (more specifically, vulcanization) and / or chain extension. That is, in one embodiment, liquid rubber is an uncured product. In addition, having fluidity means that, in one embodiment, liquid rubber dissolved in cyclohexane is placed in a vial with a body diameter of 21 mm and a total length of 50 mm at 23°C, and then dried, the liquid rubber is filled in the vial to a height of 1 mm, sealed, and the vial is left standing for 24 hours in an upside-down state, and a movement of the substance in the height direction of 0.1 mm or more can be confirmed. The liquid rubber may have a monomer composition of a general rubber, and is preferably a relatively low molecular weight from the viewpoint of ease of handling and good dispersibility of cellulose nanofibers. In one embodiment, the liquid rubber has a number average molecular weight (Mn) of 80,000 or less, thereby exhibiting a liquid form. In this disclosure, the molecular weight and molecular weight distribution of the rubber component are values obtained by measuring a chromatogram using gel permeation chromatography using three columns packed with polystyrene gel connected together, and calculating from a calibration curve using standard polystyrene. Tetrahydrofuran is used as the solvent.
[0062] When the rubber composition is cured to form a cured rubber product, it is desirable to vulcanize the liquid rubber during curing in order to improve the mechanical properties of the cured rubber product.
[0063] The number average molecular weight (Mn) of the liquid rubber is preferably 1,000 or more, or 1,500 or more, or 2,000 or more from the viewpoint of obtaining a rubber composition having excellent storage modulus and dispersibility in the matrix component in the rubber composite, and is preferably 80,000 or less, or 50,000 or less, or 40,000 or less, or 30,000 or less, or 10,000 or less in terms of having high fluidity suitable for dispersing cellulose nanofibers well in the liquid rubber and of the liquid rubber not becoming too hard after curing and having good rubber elasticity.
[0064] The weight average molecular weight (Mw) of the liquid rubber is preferably 1,000 or more, or 2,000 or more, or 4,000 or more from the viewpoint of obtaining a rubber composition having excellent storage modulus and dispersibility in the matrix component in the rubber composite, and is preferably 240,000 or less, or 150,000 or less, or 30,000 or less from the viewpoint of having high fluidity suitable for dispersing cellulose nanofibers well in the liquid rubber and of the liquid rubber not becoming too hard after curing and having good rubber elasticity.
[0065] The ratio (Mw / Mn) of the number average molecular weight (Mn) to the weight average molecular weight (Mw) of the liquid rubber is preferably 1.5 or more, or 1.8 or more, or 2.0 or more, in that a certain degree of variation in molecular weight makes it possible to achieve a high degree of compatibility between multiple properties of the rubber molded product (in one embodiment, a high degree of compatibility between the storage modulus and rubber elasticity of the rubber molded product), and is preferably 10 or less, or 8 or less, or 5 or less, in that the variation in molecular weight is not excessively large and the desired physical properties of the rubber molded product can be stably obtained.
[0066] The liquid rubber may be a conjugated diene polymer or a non-conjugated diene polymer, or a hydrogenated product thereof. The above polymer or hydrogenated product thereof may be an oligomer. In one embodiment, the liquid rubber may have reactive groups (e.g., one or more selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanato group, a thio group, an amino group, and a halo group) at both ends, and may therefore be bifunctional. These reactive groups contribute to crosslinking and / or chain extension of the liquid rubber.
[0067] [Conjugated diene polymer] The conjugated diene polymer may be a homopolymer, a copolymer of two or more conjugated diene monomers, or a copolymer of a conjugated diene monomer and another monomer. The copolymer may be either random or block.
[0068] Conjugated diene monomers include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 3-methyl-1,3-pentadiene, 1,3-heptadiene, and 1,3-hexadiene, which may be used alone or in combination of two or more.
[0069] In one embodiment, the conjugated diene polymer is a copolymer of the above-mentioned conjugated diene monomer and an aromatic vinyl monomer. The aromatic vinyl monomer is not particularly limited as long as it is a monomer copolymerizable with the conjugated diene monomer, and examples thereof include styrene, m- or p-methylstyrene, α-methylstyrene, ethylstyrene, p-tert-butylstyrene, vinylethylbenzene, vinylxylene, vinylnaphthalene, diphenylethylene, and divinylbenzene, which may be used alone or in combination of two or more. From the viewpoints of the molding processability of the rubber composite and the impact resistance of the molded article, styrene is preferred.
[0070] Examples of random copolymers include butadiene-isoprene random copolymers, butadiene-styrene random copolymers, isoprene-styrene random copolymers, and butadiene-isoprene-styrene random copolymers. The composition distribution of each monomer in the copolymer chain includes a completely random copolymer that is close to a statistically random composition, and a tapered (gradient) random copolymer that has a gradient in composition distribution. The bond type of the conjugated diene polymer, i.e., the composition of 1,4-bonds, 1,2-bonds, etc., may be uniform or different between molecules.
[0071] The block copolymer may be a copolymer consisting of two or more blocks. For example, the block copolymer may be a block copolymer in which a block A of an aromatic vinyl monomer and a block B of a conjugated diene monomer and / or a copolymer of an aromatic vinyl monomer and a conjugated diene monomer constitute a structure such as AB, ABA, or ABAB. The boundaries of the blocks do not necessarily need to be clearly distinguished. For example, when the block B is a copolymer of an aromatic vinyl monomer and a conjugated diene monomer, the aromatic vinyl monomer in the block B may be distributed uniformly or in a tapered shape. In addition, the block B may have a plurality of parts in which the aromatic vinyl monomer is distributed uniformly and / or a plurality of parts in which the aromatic vinyl monomer is distributed in a tapered shape. Furthermore, the block B may have a plurality of segments with different aromatic vinyl monomer contents. When the copolymer has a plurality of blocks A and B, the molecular weights and compositions of the blocks A and B may be the same or different.
[0072] The block copolymer may be a mixture of two or more types differing from each other in one or more of the bond type, molecular weight, aromatic vinyl compound type, conjugated diene compound type, 1,2-vinyl content or the total amount of 1,2-vinyl content and 3,4-vinyl content, aromatic vinyl compound component content, hydrogenation rate, etc.
[0073] The amount of vinyl bonds (for example, 1,2- or 3,4-bonds of butadiene) in the conjugated diene bond units in the conjugated diene polymer is preferably 10 mol % or more and 75 mol % or less, or 13 mol % or more and 65 mol % or less. The amount of vinyl bonds in the conjugated diene bond units (for example, the amount of 1,2-bonds in butadiene) is 13 It can be determined by C-NMR (quantitative mode). 13 By integrating the peak areas appearing in the following C-NMR, a value proportional to the carbon amount of each structural unit can be obtained, which can then be converted into mass % of each structural unit. Styrene 145~147ppm Vinyl 110~116ppm Diene(cis) 24~28ppm Diene (trans) 29~33ppm
[0074] In the copolymer of a conjugated diene monomer and an aromatic vinyl monomer, the amount of the aromatic vinyl monomer bonded to the conjugated diene monomer (also referred to as the aromatic vinyl bond amount in the present disclosure) may be preferably 5.0% by mass or more and 70% by mass or less, or 10% by mass or more and 50% by mass or less, based on the total mass of the conjugated diene polymer. The aromatic vinyl bond amount can be determined by the ultraviolet absorbance of the phenyl group, and the conjugated diene bond amount can also be determined based on this.
[0075] The hydrogenated product of the conjugated diene polymer may be the hydrogenated products of the conjugated diene polymers exemplified above, for example, a hydrogenated product of a butadiene homopolymer, an isoprene homopolymer, a styrene-butadiene copolymer, or an acrylonitrile-butadiene copolymer.
[0076] [Non-conjugated diene polymer] The non-conjugated diene polymer may be a homopolymer, a copolymer of two or more non-conjugated diene monomers, or a copolymer of a non-conjugated diene monomer and another monomer. The copolymer may be either random or block. Examples of the non-conjugated diene polymer include: Olefin polymers such as ethylene-propylene rubber, ethylene-propylene-diene rubber, ethylene-butene-diene rubber, and ethylene-α-olefin copolymers; Examples of the rubber include butyl rubber, brominated butyl rubber, acrylic rubber, fluororubber, silicone rubber, chlorinated polyethylene rubber, epichlorohydrin rubber, α,β-unsaturated nitrile-acrylate-conjugated diene copolymer rubber, urethane rubber, and polysulfide rubber.
[0077] In ethylene-α-olefin copolymers, monomers that can be copolymerized with ethylene units include: aliphatic substituted vinyl monomers such as propylene, butene-1, pentene-1, 4-methylpentene-1, hexene-1, heptene-1, octene-1, nonene-1, decene-1, undecene-1, dodecene-1, tridecene-1, tetradecene-1, pentadecene-1, hexadecene-1, heptadecene-1, octadecene-1, nonadecene-1, eicosene-1, and isobutylene; styrene, substituted vinyl monomers, and the like. aromatic vinyl monomers such as substituted styrene; ester vinyl monomers such as vinyl acetate, acrylic esters, methacrylic esters, glycidyl acrylic esters, glycidyl methacrylic esters, and hydroxyethyl methacrylic esters; nitrogen-containing vinyl monomers such as acrylamide, allylamine, vinyl-p-aminobenzene, and acrylonitrile; and dienes such as butadiene, cyclopentadiene, 1,4-hexadiene, and isoprene.
[0078] Preferably, it is a copolymer of ethylene and one or more α-olefins having 3 to 20 carbon atoms, more preferably a copolymer of ethylene and one or more α-olefins having 3 to 16 carbon atoms, and most preferably a copolymer of ethylene and one or more α-olefins having 3 to 12 carbon atoms. From the viewpoint of impact resistance, the molecular weight of the ethylene-α-olefin copolymer is preferably 10,000 or more, more preferably 10,000 to 100,000, more preferably 10,000 to 80,000, and even more preferably 20,000 to 60,000. From the viewpoint of achieving both fluidity and impact resistance, the molecular weight distribution (weight average molecular weight / number average molecular weight: Mw / Mn) is preferably 3 or less, and more preferably 1.8 to 2.7.
[0079] Moreover, the preferred content of ethylene units in the ethylene-α-olefin copolymer is 30 to 95% by mass based on the total amount of the ethylene-α-olefin copolymer, from the viewpoint of ease of handling during processing.
[0080] These preferred ethylene-α-olefin copolymers can be produced, for example, by the production methods described in JP-B-4-12283, JP-A-60-35006, JP-A-60-35007, JP-A-60-35008, JP-A-5-155930, JP-A-3-163088, and U.S. Pat. No. 5,272,236.
[0081] In one embodiment, the liquid rubber includes at least one selected from the group consisting of diene rubber (the conjugated diene polymer described above in one embodiment), silicone rubber, urethane rubber, polysulfide rubber, and hydrogenated products thereof.
[0082] It is advantageous for the liquid rubber to have a predetermined viscosity or less at 80° C. in order to uniformly disperse the rubber composition in the matrix rubber component in the rubber composite. The viscosity of the liquid rubber at 80° C. is preferably 1,000,000 mPa·s or less, or 500,000 mPa·s or less, or 250,000 mPa·s or less, or 100,000 mPa·s or less from the viewpoint of favorable dispersion of the rubber composition in the matrix rubber component in the rubber composite and favorable dispersion of the cellulose nanofibers in the liquid rubber, and is preferably 50 mPa·s or more, or 100 mPa·s or more, or 300 mPa·s or more from the viewpoint of obtaining a rubber composite having excellent physical properties (particularly storage modulus).
[0083] The viscosity of the liquid rubber at 25°C is preferably 1,000,000 mPa·s or less, or 500,000 mPa·s or less, or 200,000 mPa·s or less, from the viewpoint of achieving good dispersion of the cellulose nanofibers in the liquid rubber, and is preferably 100 mPa·s or more, or 300 mPa·s or more, or 500 mPa·s or more, from the viewpoint of obtaining a rubber composite having excellent physical properties (particularly storage modulus).
[0084] It is advantageous when dispersing cellulose nanofibers in the liquid rubber that the viscosity of the liquid rubber at 0° C. is a predetermined value or less. From the viewpoint of favorably dispersing cellulose nanofibers in the liquid rubber, the viscosity of the liquid rubber at 0° C. is preferably 2,000,000 mPa·s or less, or 1,000,000 mPa·s or less, or 400,000 mPa·s or less, and from the viewpoint of obtaining a rubber composite having excellent physical properties (particularly storage modulus), the viscosity is preferably 200 mPa·s or more, or 600 mPa·s or more, or 1,000 mPa·s or more.
[0085] It is preferable that the viscosity of the liquid rubber has a small temperature dependency, since this allows the cellulose nanofibers to be well dispersed in the liquid rubber over a wide range of mixing temperatures. From this viewpoint, it is particularly preferable that the viscosity of the liquid rubber at all of 80°C, 25°C, and 0°C is within the above range.
[0086] The viscosity of the liquid rubber is a value measured using a Brookfield viscometer at a rotation speed of 10 rpm.
[0087] The content of liquid rubber in the rubber composition is, from the viewpoint of obtaining the above-mentioned advantages of the liquid rubber, preferably 0.1% by mass or more, or 0.5% by mass or more, or 1% by mass or more, or 5% by mass or more, or 10% by mass or more, and, from the viewpoint of containing an appropriate amount of other components (such as cellulose nanofibers) and obtaining the advantages of these components, preferably 99% by mass or less, or 95% by mass or less, or 90% by mass or less, or 80% by mass or less, or 70% by mass or less, or 60% by mass or less, or 50% by mass or less.
[0088] In the rubber composition, the mass ratio of the cellulose nanofibers to 100 parts by mass of the total of the cellulose nanofibers and the liquid rubber is, in one embodiment, 1 part by mass or more, or 5 parts by mass or more, or 10 parts by mass or more, or 20 parts by mass or more, or 30 parts by mass or more, or 33 parts by mass or more, or 40 parts by mass or more, or 50 parts by mass or more, and in another embodiment, 99 parts by mass or less, or 95 parts by mass or less, or 90 parts by mass or less, or 80 parts by mass or less, or 70 parts by mass or less, or 60 parts by mass or less, or 50 parts by mass or less.
[0089] <Surfactant> In one embodiment, the rubber composition includes a surfactant. In one embodiment, the surfactant is a nonionic surfactant, a cationic surfactant, or a combination thereof. As the surfactant, a nonionic surfactant is preferable from the viewpoint of heat resistance. The nonionic surfactant and the cationic surfactant can enter the voids of the cellulose nanofiber aggregate to make the aggregate porous. For example, when the wet aggregate is impregnated with a nonionic surfactant and / or a cationic surfactant and then dried to form a dried body, shrinkage during drying can be reduced compared to a dried body obtained by drying the aggregate without using the nonionic surfactant and the cationic surfactant, and the cellulose nanofibers are well dispersed when the dried body is mixed with liquid rubber.
[0090] The nonionic surfactant is preferably a compound having a hydrophilic group selected from the group consisting of a hydroxyl group, a carboxyl group, a sulfonic acid group, and an amino group, and a hydrocarbon group.
[0091] In one embodiment, the nonionic surfactant has an aliphatic group having 6 to 30 carbon atoms as the hydrophobic portion. The cellulose nanofibers of this embodiment typically form loose aggregates, and the nonionic surfactant has good affinity with the rubber component due to the contribution of the carbon chain of the hydrophobic portion, and since the carbon chain of the hydrophobic portion is not too long, it can easily enter the voids of the cellulose nanofiber aggregate to make the aggregate porous. For example, when the nonionic surfactant is impregnated into the wet aggregate and then dried to form a dried body, shrinkage during drying can be reduced compared to a dried body obtained by drying the aggregate without using the nonionic surfactant, and the cellulose nanofibers are well dispersed when the dried body is mixed with a rubber component.
[0092] The aliphatic group may be linear or alicyclic, or a combination thereof. From the viewpoint of obtaining good dispersibility of the cellulose nanofiber in the rubber component, the number of carbon atoms of the aliphatic group is, in one aspect, 6 or more, or 8 or more, or 10 or more, and from the viewpoint of penetrating into the voids of the cellulose nanofiber aggregate, in one aspect, 30 or less, or 25 or less, or 20 or less.
[0093] The nonionic surfactant preferably has one or more structures selected from the group consisting of oxyethylene, glycerol, and sorbitan (specifically, a repeating structure having one or more of these repeating units) as a hydrophilic portion. These structures are preferred in that they exhibit high hydrophilicity and can easily produce various nonionic surfactants in combination with various hydrophobic portions. In the nonionic surfactant having the hydrophilic portion, the carbon number n of the hydrophobic portion and the number of repeating units m of the hydrophilic portion preferably satisfy the following formula: n>m, from the viewpoint of obtaining good dispersibility of the cellulose nanofibers in the rubber component. The repeating number m of the hydrophilic portion is preferably 1 or more, or 2 or more, or 3 or more, or 5 or more, from the viewpoint of good penetration of the nonionic surfactant into the voids of the cellulose nanofiber aggregate, and is preferably 30 or less, or 25 or less, or 20 or less, or 18 or less, from the viewpoint of obtaining good dispersibility of the cellulose nanofibers in the rubber component.
[0094] The nonionic surfactant is preferably The following general formula (1): R-(OCH2CH2) m -OH (1) [wherein R represents a monovalent aliphatic group having 6 to 30 carbon atoms, and m is a natural number smaller than the number of carbon atoms in R], and The following general formula (2): R1OCH2-(CHOH)4-CH2OR2(2) [wherein R1 and R2 each independently represent a hydrogen atom, an aliphatic group having 1 to 30 carbon atoms, -COR3 {wherein R3 represents an aliphatic group having 1 to 30 carbon atoms}, or -(CH2CH2O)y -R4 {wherein R4 represents a hydrogen atom or an aliphatic group having 1 to 30 carbon atoms, and y represents an integer of 1 to 30.}, The compound is one or more selected from the group consisting of:
[0095] In general formula (1), R corresponds to the hydrophobic portion described above, and (OCH2CH2) (i.e., oxyethylene unit) corresponds to the hydrophilic portion described above. The carbon number of R and the repeat number m of (OCH2CH2) are preferably in the same range as the carbon number n of the hydrophobic portion and the repeat number m of the hydrophilic portion described above, respectively.
[0096] In general formula (2), for each of R1, R2, R3, and R4, the number of carbon atoms in the aliphatic group having 1 to 30 carbon atoms is preferably 6 or more, or 8 or more, or 10 or more, and preferably 24 or less, or 20 or less, or 18 or less. Furthermore, y is 1 or more, preferably 2 or more, or 4 or more, and preferably 30 or less, or 25 or less, or 20 or less.
[0097] Examples of cationic surfactants include benzalkonium chloride, alkyltrimethylammonium chloride, stearyldimethylammonium chloride, stearyltrimethylammonium chloride, lanolin fatty acid aminopropylethyldimethylammonium ethyl sulfate, stearyldimethylbenzylammonium chloride, stearylamine acetate, and coconutamine acetate.
[0098] The amount of surfactant, or the amount of nonionic surfactant, or the amount of cationic surfactant, or the total amount of nonionic surfactant and cationic surfactant in the rubber composition is, per 100 parts by mass of cellulose nanofiber, preferably 10 parts by mass or more, or 15 parts by mass or more, or 20 parts by mass or more, and preferably 200 parts by mass or less, or 150 parts by mass or less, or 100 parts by mass or less, or 90 parts by mass or less, or 80 parts by mass or less, or 70 parts by mass or less, or 60 parts by mass or less, or 50 parts by mass or less, or 45 parts by mass or less, or 40 parts by mass or less.
[0099] <Additional Ingredients> The rubber composition may further contain additional components in addition to the above-mentioned cellulose nanofibers, liquid rubber, and surfactant. Examples of the additional components include additional polymers, dispersants, organic or inorganic fillers, heat stabilizers, antioxidants, antistatic agents, colorants, and the like. Examples of the additional polymers include rubber components and thermoplastic elastomers exemplified below as matrix components of the rubber composite. The content ratio of any additional component in the rubber composition is appropriately selected within a range that does not impair the desired effects of the present invention, and may be, for example, 0.01 to 50 mass %, or 0.1 to 30 mass %.
[0100] <Production of Rubber Composition> The method for producing the rubber composition is not particularly limited. The components constituting the rubber composition may be mixed with stirring means such as a rotation-revolution mixer, a planetary mixer, a homogenizer, a propeller type stirrer, a rotary stirrer, an electromagnetic stirrer, an open roll, a Banbury mixer, a single screw extruder, or a twin screw extruder to obtain the rubber composition. In addition, the components may be stirred under heating in order to efficiently perform shearing. A mixing method using a homogenizer is preferred because it can promote dispersion by applying high shearing force and pressure. The order of adding the components during mixing is not limited, but for example, (1) A method of simultaneously adding and mixing cellulose nanofibers, a surfactant, a liquid rubber, and optionally other components to obtain a rubber composition; (2) A method in which components other than the liquid rubber are mixed in advance to obtain a premixture, and then the premixture is mixed with the liquid rubber to obtain a rubber composition. etc. As the above method (2), for example, The cellulose nanofibers are mixed with a surfactant to allow the surfactant to penetrate into the voids in the cellulose nanofiber aggregates, Next, liquid rubber is added and mixed to allow the liquid rubber to penetrate into the voids. Methods include: In the above method (2), after the premix is obtained, the premix may be dried before mixing with the liquid rubber. Also, after the rubber composition is obtained, it may be dried, and the drying conditions may be controlled to form a powder, which will be described later.
[0101] ≪Powder≫ One aspect of the present disclosure provides a powder comprising the rubber composition of the present disclosure. The powder may have one or more of the following properties, which may provide the powder with excellent processing properties and allow the cellulose nanofibers to exhibit an excellent dispersion state in the rubber component:
[0102] <Surface condition of cellulose nanofiber> In the powder according to one embodiment, it is preferable that at least a part of the surface of the cellulose nanofiber is covered with the first rubber component in order to facilitate dispersion of the cellulose nanofiber without aggregation in the second or third rubber component when kneaded with the rubber component. In one embodiment, the state in which at least a part of the surface of the cellulose nanofiber is covered with the first rubber component is a state in which the first rubber component and the cellulose nanofiber are in direct contact with each other, and the average length of the contact portion is at least twice the average fiber diameter of the cellulose nanofiber. The state in which the surface of the cellulose nanofiber in the powder is covered with the first rubber component is observed with an electron microscope (scanning electron microscope in one embodiment) or an atomic force microscope, and when it is possible to confirm with both an electron microscope and an atomic force microscope, it is confirmed with an electron microscope. The above average fiber diameter is a value measured by the method of the present disclosure using the powder as a measurement sample. The above average length of the contact portion is measured with an electron microscope (scanning electron microscope in one embodiment) or an atomic force microscope using the powder as a measurement sample. Specifically, in an observation field where the magnification is adjusted so that at least 30 cellulose nanofibers can be observed, the length of the contact area with the first rubber component is measured for each of 30 randomly selected cellulose nanofibers, and the number average is calculated. The number average is then calculated for the 30 fibers to determine the average length of the contact area.
[0103] <Loose bulk density> In one embodiment, the loose bulk density of the powder is preferably 0.01 g / cm from the viewpoints of good powder flowability, excellent feedability to a kneader, and suppression of migration of a surfactant to rubber. 3 or more than 0.05g / cm 3 or more than 0.10g / cm 3 or more than 0.15g / cm 3 or more than 0.20g / cm 3 The powder is preferably 0.50 g / cm or more in that the powder is easily disintegrated in the rubber so that the cellulose nanofibers can be well dispersed in the rubber, and the powder is not too heavy so that poor mixing of the powder and the rubber can be avoided. 3 or less than 0.40g / cm3 or less than 0.30g / cm 3 or less than 0.25g / cm 3 or less than 0.20g / cm 3 The following is the summary.
[0104] <Packed bulk density> The packed bulk density of the powder is controlled to a range that is useful for controlling the loose bulk density and compressibility to a suitable range, and in one embodiment, preferably is 0.01 g / cm 3 or more than 0.05g / cm 3 or more than 0.10g / cm 3 or more than 0.15g / cm 3 or more than 0.20g / cm 3 More preferably, it is 1.00 g / cm 3 or less than 0.80g / cm 3 or less than 0.70g / cm 3 or less than 0.60g / cm 3 or less than 0.50g / cm 3 or less than 0.40g / cm 3 or less than 0.30g / cm 3 The following is the result.
[0105] The loose bulk density and packed bulk density are values measured using a powder tester (model: PT-X) manufactured by Hosokawa Micron Corporation according to the procedure described in the section [Examples] of this disclosure.
[0106] An example of a method for producing a powder includes a slurry preparation step of preparing a slurry containing cellulose nanofibers and a liquid medium, and a drying step of drying the slurry to form a powder.
[0107] (Slurry preparation process) In this step, a slurry is prepared. As the liquid medium, a water-miscible organic solvent, for example: alcohols having a boiling point of 50°C to 170°C (e.g., methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, s-butanol, t-butanol, etc.); ethers (e.g., propylene glycol monomethyl ether, 1,2-dimethoxyethane, diisopropyl ether, tetrahydrofuran, 1,4-dioxane, etc.); carboxylic acids (e.g., formic acid, acetic acid, lactic acid, etc.); esters (e.g., ethyl acetate, vinyl acetate, etc.); ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, etc.); nitrogen-containing solvents (dimethylformamide, dimethylacetamide, acetonitrile, etc.), etc. can be used. In a typical embodiment, the liquid medium in the slurry is substantially only water. The slurry may be composed of cellulose nanofibers and a liquid medium, or may contain a surfactant and / or a first rubber component, and may further contain any additional components.
[0108] The concentration of cellulose nanofibers in the slurry is preferably 5% by mass or more, or 10% by mass or more, or 15% by mass or more, or 20% by mass or more, or 25% by mass or more from the viewpoint of process efficiency in the subsequent drying step, and is preferably 60% by mass or less, or 55% by mass or less, or 50% by mass or less, or 45% by mass or less from the viewpoint of maintaining good handleability by avoiding an excessive increase in the viscosity of the slurry and solidification due to aggregation. For example, cellulose nanofibers are often produced in a dilute dispersion, and the cellulose nanofiber concentration in the slurry may be adjusted to the above-mentioned preferred range by concentrating such a dilute dispersion. For concentration, methods such as suction filtration, pressure filtration, centrifugal deliquation, and heating can be used.
[0109] (drying process) In this step, the slurry is dried under controlled drying conditions to form a powder. Components other than cellulose nanofibers may be added before, during, and / or after drying of the slurry. Drying can be performed using drying devices such as a spray dryer or an extruder. The drying device may be a commercially available product, and examples of the drying device include a micromist spray dryer (manufactured by Fujisaki Electric), a spray dryer (manufactured by Okawara Kakoki), and a twin-screw extruder (manufactured by Japan Steel Works). Among the drying conditions, appropriately controlling the drying speed, drying temperature, and / or pressure (degree of reduced pressure), especially the drying speed, can be advantageous in achieving the desired shape of the powder.
[0110] The drying speed, which is the amount (parts by mass) of liquid medium desorbed per minute per 100 parts by mass of slurry, may be, for example, 10% / min or more, or 50% / min or more, or 100% / min or more, from the viewpoint of forming a powder of the desired particle size by rapidly drying the slurry, and may be, for example, 10,000% / min or less, or 1,000% / min or less, or 500% / min or less, from the viewpoint of suppressing aggregation of the cellulose nanofibers and obtaining good handleability by avoiding excessive pulverization of the cellulose nanofibers. The drying speed is calculated by the following formula: Drying rate (% / min) = (slurry moisture content at start of drying (mass%) - powder moisture content at end of drying (mass%)) / time required from start of drying to end of drying (min) (i.e., the average value throughout the drying process). Here, the start of drying refers to the time when the process of supplying the slurry or cake to be dried to the device and drying at the intended drying temperature, degree of vacuum, and shear rate begins, and the time for premixing under conditions where the drying temperature, degree of vacuum, and shear rate are different from those in the drying process is not included in the drying time. The end point of drying refers to the point at which the moisture content first becomes 7% by mass or less when sampling is performed at intervals of at most 10 minutes from the start of drying. In the case of a continuous drying device, the time required from the start of drying to the end of drying can be interpreted as the residence time. In the case of a spray dryer, the residence time can be calculated from the heating air volume and the volume of the drying chamber. In addition, when an extruder is used as a drying device, the residence time can be calculated from the screw rotation speed and the total pitch number of the screw.
[0111] The drying temperature may be, for example, 20°C or more, or 30°C or more, or 40°C or more, or 50°C or more from the viewpoints of drying efficiency and of appropriately agglomerating the cellulose nanofibers to form a powder of the desired particle size, and may be, for example, 200°C or less, or 150°C or less, or 140°C or less, or 130°C or less, or 100°C or less from the viewpoints of preventing thermal degradation of the cellulose nanofibers and additional components and avoiding excessive pulverization of the cellulose nanofibers. The drying temperature is the temperature of the heat source in contact with the slurry, and is defined, for example, as the surface temperature of the temperature-regulating jacket of the drying device, the surface temperature of the heating cylinder, or the temperature of the hot air.
[0112] The degree of reduced pressure may be -1 kPa or less, or -10 kPa or less, or -20 kPa or less, or -30 kPa or less, or -40 kPa or less, or -50 kPa or less from the viewpoints of drying efficiency and moderately agglomerating the cellulose nanofibers to form a powder of the desired particle size, and may be -100 kPa or more, or -95 kPa or more, or -90 kPa or more from the viewpoint of avoiding excessive pulverization of the cellulose nanofibers.
[0113] In the drying step, the residence time of the slurry at a temperature of 20° C. to 200° C. may be set to preferably 0.01 to 10 minutes, or 0.05 to 5 minutes, or 0.1 to 2 minutes. Drying under such conditions rapidly dries the cellulose nanofibers, and a powder of the desired particle size is successfully produced.
[0114] For example, when a spray dryer is used, the slurry is sprayed and introduced into a drying chamber in which hot gas is circulated using a spray mechanism (rotating disk, pressure nozzle, etc.) and dried. The size of the slurry droplets when sprayed may be, for example, 0.01 μm to 500 μm, or 0.1 μm to 100 μm, or 0.5 μm to 10 μm. The hot gas may be an inert gas such as nitrogen or argon, or air, etc. The hot gas temperature may be, for example, 50° C. to 300° C., or 80° C. to 250° C., or 100° C. to 200° C. The contact between the slurry droplets and the hot gas in the drying chamber may be a parallel flow, a counter flow, or a parallel counter flow. The particulate powder generated by drying the droplets is collected by a cyclone, a drum, or the like.
[0115] Also, for example, when an extruder is used, the slurry is fed from a hopper into a kneading section equipped with a screw, and the slurry is continuously transported by the screw in the kneading section under reduced pressure and / or heating to dry the slurry. As for the screw mode, a conveying screw, a counterclockwise screw, and a kneading disk may be combined in any order. The drying temperature may be, for example, 50°C to 300°C, or 80°C to 250°C, or 100°C to 200°C.
[0116] <Master batch> An embodiment of the present disclosure provides a masterbatch including the rubber composition of the present disclosure. In one embodiment, the masterbatch is a mixture of the powder of the present disclosure and a second rubber component.
[0117] <Second rubber component> The second rubber component may be a natural rubber, a conjugated diene polymer, a non-conjugated diene polymer, or a hydrogenated product thereof. The above polymer or the hydrogenated product thereof may be an oligomer. The monomer composition of the second rubber component may be the same as that described above for the liquid rubber. The second rubber component may be the above-mentioned liquid rubber, or may be a rubber that is not a liquid rubber.
[0118] The conjugated diene polymer as the second rubber component constituting the matrix component may be partially or completely hydrogenated. The hydrogenation rate of the hydrogenated product is preferably 50% or more, 80% or more, or 98% or more from the viewpoint of suppressing thermal degradation during processing, and is preferably 50% or less, 20% or less, or 0% (i.e., non-hydrogenated product) from the viewpoint of low temperature toughness.
[0119] In the conjugated diene polymer as the second rubber component constituting the matrix component, the amount of vinyl bonds (e.g., 1,2- or 3,4-bonds of butadiene) in the conjugated diene bond units is, from the viewpoint of suppressing crystallization of the soft segment, preferably 5 mol % or more, or 10 mol % or more, or 13 mol % or more, or 15 mol % or more, and preferably 80 mol % or less, or 75 mol % or less, or 65 mol % or less, or 50 mol % or less, or 40 mol % or less.
[0120] In a preferred embodiment, the second rubber component includes one or more selected from the group consisting of styrene-butadiene rubber, butadiene rubber, and isoprene rubber.
[0121] The number average molecular weight (Mn) of the second rubber component is preferably 100,000 or more, or 150,000 or more, or 200,000 or more from the viewpoint of obtaining a rubber composite having excellent storage modulus, etc., and is preferably 800,000 or less, or 750,000 or less, or 700,000 or less, or 600,000 or less from the viewpoint of easiness of dispersion of cellulose nanofibers in the second rubber component and the fact that the second rubber component does not become too hard after curing and has good rubber elasticity.
[0122] [Modified rubber] The second rubber component may be a modified rubber, and for example, in the conjugated diene polymer or non-conjugated diene polymer exemplified above, a modified group such as an epoxy group, an acid anhydride group, a carboxy group, an aldehyde group, a hydroxyl group, an alkoxy group, an amino group, an amide group, an imide group, a nitro group, an isocyanate group, or a mercapto group may be introduced. Examples of modified rubber include epoxy modified natural rubber, epoxy modified butadiene rubber, epoxy modified styrene butadiene rubber, carboxy modified natural rubber, carboxy modified butadiene rubber, carboxy modified styrene butadiene rubber, acid anhydride modified natural rubber, acid anhydride modified butadiene rubber, and acid anhydride modified styrene butadiene rubber.
[0123] The amount of the modifying group relative to 100 mol% of all monomer units is preferably 0.1 mol% or more, or 0.2 mol% or more, or 0.3 mol% or more, and preferably 5 mol% or less, or 3 mol% or less, from the viewpoint of affinity between the cellulose nanofiber and the second rubber component. The amount of the modifying group can be confirmed by a method of calculating the molar ratio of the modifying group by combining a previously specified monomer composition with the quantification by elemental analysis of elements not contained in the unmodified rubber.
[0124] In the masterbatch, the content of the second rubber component is preferably 20% by mass or more, or 30% by mass or more, or 40% by mass or more, and preferably 99% by mass or less, or 95% by mass or less, or 90% by mass or less.
[0125] [Thermoplastic elastomer] In one embodiment, the second rubber component may include or be a thermoplastic elastomer. In the present disclosure, an elastomer is, in one embodiment, a substance (specifically, a natural or synthetic polymer substance) that is elastic at room temperature (23°C). In addition, being elastic in one embodiment means that the storage modulus at 23°C and 10 Hz measured by dynamic viscoelasticity measurement is 1 MPa or more and 100 MPa or less. The thermoplastic elastomer may be a conjugated diene polymer or a non-conjugated diene polymer, and in one embodiment, is a crosslinked product. The suitable monomer composition of the thermoplastic elastomer may be the same as that described above in the above sections (conjugated diene polymer) and (non-conjugated diene polymer).
[0126] The number average molecular weight (Mn) of the thermoplastic elastomer is preferably from 10,000 to 500,000, or from 40,000 to 250,000, from the viewpoint of achieving both impact strength and fluidity.
[0127] The thermoplastic elastomer may have a core-shell structure. Examples of elastomers having a core-shell structure include core-shell type elastomers having a core that is a particulate rubber and a shell that is a glassy graft layer formed on the outside of the core. The core is preferably a butadiene rubber, an acrylic rubber, a silicone-acrylic composite rubber, or the like. The shell is preferably a glassy polymer such as a styrene resin, an acrylonitrile-styrene copolymer, or an acrylic resin.
[0128] From the viewpoint of having even better compatibility with the rubber composition, the thermoplastic elastomer is preferably at least one selected from the group consisting of styrene-butadiene block copolymers, styrene-ethylene-butadiene block copolymers, styrene-ethylene-butylene block copolymers, styrene-butadiene-butylene block copolymers, styrene-isoprene block copolymers, styrene-ethylene-propylene block copolymers, styrene-isobutylene block copolymers, hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-ethylene-butadiene block copolymers, hydrogenated styrene-butadiene-butylene block copolymers, hydrogenated styrene-isoprene block copolymers, and homopolymers of styrene (polystyrene), and more preferably at least one selected from the group consisting of styrene-butadiene block copolymers, hydrogenated styrene-butadiene block copolymers, and polystyrene.
[0129] In one embodiment, at least a part of the thermoplastic elastomer may have an acidic functional group. In the present disclosure, when the thermoplastic elastomer has an acidic functional group, it means that the acidic functional group is added to the molecular skeleton of the elastomer via a chemical bond. In the present disclosure, the acidic functional group means a functional group capable of reacting with a basic functional group, etc., and specific examples thereof include a hydroxyl group, a carboxyl group, a carboxylate group, a sulfo group, and an acid anhydride group.
[0130] From the viewpoint of affinity between cellulose nanofibers and the elastomer component, the amount of acidic functional groups added in the elastomer is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.2% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less, based on 100% by mass of the elastomer. The number of acidic functional groups is a value obtained by measuring a calibration curve sample in which an acidic substance has been mixed in advance using an infrared absorption spectrometer, and measuring the sample based on a calibration curve that has been prepared using the characteristic absorption band of the acid.
[0131] Examples of elastomers having an acidic functional group include elastomers having a core-shell structure having a shell layer formed using acrylic acid or the like as a copolymerization component, and elastomers which are modified products obtained by grafting an α,β-unsaturated dicarboxylic acid or a derivative thereof to an ethylene-α-olefin copolymer, polyolefin, aromatic compound-conjugated diene copolymer, or a hydrogenated aromatic compound-conjugated diene copolymer containing acrylic acid or the like as a monomer, in the presence or absence of a peroxide.
[0132] In a preferred embodiment, the elastomer is an anhydride modified elastomer.
[0133] Among these, modified products obtained by grafting an α,β-unsaturated dicarboxylic acid or a derivative thereof onto a polyolefin, an aromatic compound-conjugated diene copolymer, or a hydrogenated aromatic compound-conjugated diene copolymer in the presence or absence of a peroxide are more preferred, and among these, modified products obtained by grafting an α,β-unsaturated dicarboxylic acid or a derivative thereof onto an ethylene-α-olefin copolymer, or a hydrogenated aromatic compound-conjugated diene block copolymer in the presence or absence of a peroxide are particularly preferred.
[0134] Specific examples of the α,β-unsaturated dicarboxylic acid and its derivatives include maleic acid, fumaric acid, maleic anhydride, and fumaric anhydride, with maleic anhydride being particularly preferred.
[0135] In one embodiment, the elastomer may be a mixture of an elastomer having an acidic functional group and an elastomer not having an acidic functional group. When the total of the elastomer having an acidic functional group and the elastomer not having an acidic functional group is 100% by mass, the mixing ratio of the elastomer having an acidic functional group is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, and most preferably 40% by mass or more, from the viewpoint of maintaining high toughness and physical property stability of the rubber composite. There is no particular upper limit, and substantially all of the elastomer may be an elastomer having an acidic functional group, but from the viewpoint of not causing problems in flowability, it is desirable to have 80% by mass or less.
[0136] The content of the thermoplastic elastomer in the masterbatch is preferably 20% by mass or more, or 30% by mass or more, and preferably 99% by mass or less, or 95% by mass or less, or 90% by mass or less.
[0137] <Vulcanizing agents, vulcanization accelerators> When the master batch contains uncured rubber, the master batch typically contains a vulcanizing agent and may optionally contain a vulcanization accelerator. As the vulcanizing agent and vulcanization accelerator, a conventionally known one may be appropriately selected according to the type of uncured rubber in the master batch. As the vulcanizing agent, organic peroxides, azo compounds, oxime compounds, nitroso compounds, polyamine compounds, sulfur, sulfur compounds, etc. can be used. As the sulfur compounds, sulfur monochloride, sulfur dichloride, disulfide compounds, polymeric polysulfur compounds, etc. can be mentioned. The amount of the vulcanizing agent is preferably 0.01 parts by mass to 20 parts by mass, or 0.1 parts by mass to 15 parts by mass, based on 100 parts by mass of the uncured rubber in the master batch.
[0138] Examples of the vulcanization accelerator include sulfenamide-based, guanidine-based, thiuram-based, aldehyde-amine-based, aldehyde-ammonia-based, thiazole-based, thiourea-based, and dithiocarbamate-based vulcanization accelerators. Zinc oxide, stearic acid, and the like may be used as a vulcanization aid. The amount of the vulcanization accelerator is preferably 0.01 to 20 parts by mass, or 0.1 to 15 parts by mass, based on 100 parts by mass of the uncured rubber in the master batch.
[0139] [Rubber additives] The master batch may contain various conventionally known rubber additives (stabilizers, softeners, antioxidants, etc.). As the rubber stabilizer, one or more antioxidants such as 2,6-di-tert-butyl-4-hydroxytoluene (BHT), n-octadecyl-3-(4'-hydroxy-3',5'-di-tert-butylphenyl)propionate, and 2-methyl-4,6-bis[(octylthio)methyl]phenol may be used. As the rubber softener, one or more process oils, extender oils, etc. may be used. However, the master batch of the present embodiment can form a flexible molded body in one embodiment, and therefore may not contain a rubber softener in one embodiment.
[0140] <Additional Ingredients> The masterbatch may further contain additional components as necessary to improve its performance. Examples of the additional components include dispersants, organic or inorganic fillers, heat stabilizers, antioxidants, antistatic agents, colorants, etc. The content ratio of any additional component in the masterbatch is appropriately selected within a range that does not impair the desired effects of the present invention, and may be, for example, 0.01 to 50% by mass, or 0.1 to 30% by mass.
[0141] In a preferred embodiment, the master batch contains 10 to 50 parts by mass of cellulose nanofibers, or 15 to 40 parts by mass, or 20 to 30 parts by mass, and 1 to 50 parts by mass, or 2 to 40 parts by mass, or 3 to 30 parts by mass of a surfactant, relative to 100 parts by mass of the rubber component. The amount of the rubber component is the total amount of the rubber components present in the master batch (in one embodiment, the total amount of the first rubber component and the second rubber component). In one embodiment, the component composition of the master batch may be the same as that described above for the rubber composition. In the master batch, the mass ratio (master batch / additional component) of the additional component (in one embodiment, the second rubber component) may be 1 / 99 to 99 / 1, or 5 / 95 to 95 / 5, or 10 / 90 to 90 / 10, or 20 / 80 to 80 / 20, or 30 / 70 to 70 / 30, or 40 / 60 to 60 / 40.
[0142] One aspect of the present disclosure provides a method for producing a masterbatch, which includes a step of kneading the powder of the present disclosure with a second rubber component to obtain a masterbatch. The kneading conditions are not particularly limited, but for example, a kneader used in general rubber kneading, such as a Banbury mixer or an open roll, can be used.
[0143] <Rubber composite> One aspect of the present disclosure also provides a rubber composite comprising (in one aspect, obtained by mixing) the rubber composition of the present embodiment and a matrix component (i.e., a component other than the rubber composition). In a typical aspect, the rubber composite is derived from the powder or masterbatch of the present disclosure. In one aspect, the rubber composite comprises the cellulose nanofibers, the liquid rubber, and the surfactant, and further comprises a third rubber component and, optionally, an additional component as a matrix component. The third rubber component may be one or more selected from the group consisting of uncured rubber and thermoplastic elastomer.
[0144] In one embodiment, the rubber composite is a mixture of the powder or master batch of the present disclosure and a third rubber component. A specific preferred embodiment of the third rubber component may be the same as that described above for the second rubber component. The first, second and third rubber components may be different from each other (different types) in one or more of the constituent monomer component type, the constituent monomer component ratio and the molecular weight, or the constituent monomer component type, the constituent monomer component ratio and the molecular weight may be the same (same type) in two or more of the first, second and third rubber components. In a preferred embodiment of the rubber composite, at least a part of the surface of the cellulose nanofiber is coated with the first rubber component. The state of the coating is confirmed by the above-mentioned scanning electron microscope observation or atomic force microscope. However, in the case where the first rubber component is indistinguishable from the second and / or third rubber components by either scanning electron microscope observation or atomic force microscope observation, if at least a part of the surface of the cellulose nanofiber is covered by the indistinguishable rubber component, at least a part of the surface may be considered to be covered by the first rubber component. In such a case, the first rubber component and the second and / or third rubber component are the same type, or are different types but have very similar properties. Therefore, it is considered that the advantage obtained when the first rubber component covers the cellulose nanofiber can be realized by the indistinguishable rubber component covering the cellulose nanofiber.
[0145] In one embodiment, the mass ratio of the powder to the third rubber component (powder / third rubber component) may be 1 / 99 to 99 / 1, or 5 / 95 to 95 / 5, or 10 / 90 to 90 / 10, or 20 / 80 to 80 / 20, or 30 / 70 to 70 / 30, or 40 / 60 to 60 / 40.
[0146] In one embodiment, the mass ratio of the masterbatch to the third rubber component (masterbatch / third rubber component) may be 1 / 99 to 99 / 1, or 5 / 95 to 95 / 5, or 10 / 90 to 90 / 10, or 20 / 80 to 80 / 20, or 30 / 70 to 70 / 30, or 40 / 60 to 60 / 40.
[0147] The rubber composite can be produced by a method including a step of kneading the powder of the present disclosure with a third rubber component, or forming a masterbatch by the method of producing a masterbatch of the present disclosure and then kneading the masterbatch with a third rubber component to obtain a rubber composite. The kneading conditions are not particularly limited, but for example, a kneader used in general rubber kneading, such as a Banbury mixer or an open roll, can be used.
[0148] The cellulose nanofiber content in the rubber composite is preferably 0.5% by mass or more, or 1% by mass or more, or 2% by mass or more, and preferably 30% by mass or less, or 20% by mass or less, or 15% by mass or less, or 10% by mass or less.
[0149] The total content of the polymer components in the rubber composite (in one embodiment, the total content of the first, second and third rubber components) is preferably 1 mass% or more, or 2 mass% or more, or 5 mass% or more, and preferably 99 mass% or less, or 95 mass% or less, or 90 mass% or less.
[0150] The mass ratio of cellulose nanofiber to the total of the polymer components in the rubber composite is preferably 1 / 99 to 50 / 50, or 2 / 98 to 40 / 60, or 3 / 97 to 30 / 70.
[0151] The surfactant content in the rubber composite may be, in one embodiment, 0.1% by weight or more, or 0.5% by weight or more, or 1% by weight or more, and in one embodiment, 10% by weight or less, or 5% by weight or less, or 1% by weight or less.
[0152] In a rubber composite according to one embodiment, the amount of vulcanizing agent and / or vulcanization accelerator relative to the uncured rubber in the rubber composite may be in the same range as the amount of vulcanizing agent and / or vulcanization accelerator relative to the uncured rubber in the masterbatch.
[0153] In a rubber composite according to one embodiment, the amounts of the rubber additives and additional components in the rubber composite may be in the same ranges as those exemplified as the amounts in the masterbatch.
[0154] <Rubber cured product and molded product> One aspect of the present disclosure provides a rubber cured product, which is a cured product of a curable component containing the rubber composition of the present disclosure. In one aspect, a desired molded body can be produced by molding the rubber composition of the present disclosure together with other desired components into a desired shape. In one aspect, the rubber composition of the present disclosure may be mixed with a third rubber component and optionally additional components to form a rubber composite, and the rubber composite may be further molded into a desired shape alone or together with other components to produce a desired molded body. The method of combining the compounded components and the molding method are not particularly limited and may be selected depending on the desired molded body. Molding methods include, but are not limited to, (1) A method for obtaining a molded article containing a cured rubber by curing a rubber composition or a masterbatch containing an uncured rubber before, during and / or after molding the rubber composition or the masterbatch alone or together with an additional component; (2) A method in which the rubber composition contains uncured rubber, the uncured rubber in the rubber composition is cured to form a cured rubber master batch, and the master batch is then molded together with additional components to obtain a molded product. (3) A method in which the rubber component in the rubber composition is a thermoplastic elastomer, and the rubber composition is melt-molded alone or together with an additional component to obtain a molded product. The molding may be carried out by injection molding, extrusion molding, extrusion profile molding, blow molding, compression molding, or the like.
[0155] In the above method (2), the mass ratio of the masterbatch to the additional component in the cured rubber product may be, for example, 1 / 99 to 99 / 1, or 5 / 95 to 95 / 5, or 10 / 90 to 90 / 10, or 20 / 80 to 80 / 20, or 30 / 70 to 70 / 30, or 40 / 60 to 60 / 40.
[0156] In one embodiment, the cured rubber product is a cured product of the rubber composite of the present disclosure. In one embodiment, the cured rubber product can be produced by a method including a step of obtaining a rubber composite by the method of producing a rubber composite of the present disclosure, and a step of curing the rubber composite to obtain a cured rubber product. In one embodiment, the cured rubber product can be obtained by a vulcanization press conforming to JIS K6299.
[0157] The cured rubber may be formed into molded articles of various shapes. The molded articles can be used in a wide range of applications, such as industrial machine parts, general machine parts, automobile, railway, vehicle, ship, and aerospace-related parts, electronic and electrical parts, building and civil engineering materials, daily necessities, sports and leisure goods, wind power generation housing parts, containers and packaging parts, etc. Examples of applications include automobile parts (for example, exterior parts such as tires, bumpers, fenders, door panels, various moldings, emblems, engine hoods, wheel caps, roofs, spoilers, and various aero parts, and interior parts such as instrument panels, console boxes, and trims), battery parts (automotive secondary battery parts, lithium ion secondary battery parts, fuel cases for solid methanol batteries, piping for fuel cells, etc.), electronic and electrical equipment parts (for example, various computers and their peripherals, junction boxes, various connectors, various office automation equipment, televisions, videos, disc players, chassis, refrigerators, air conditioners, parts for liquid crystal projectors, etc.), and daily necessities (shoe outsoles, etc.).
[0158] One aspect of the present disclosure provides a shoe outsole, a tire, a vibration-proof rubber, or a power transmission belt comprising the rubber cured product of the present disclosure. EXAMPLES
[0159] The following examples further illustrate exemplary embodiments of the present invention, but the present invention is not limited to these examples.
[0160] Evaluation method <Liquid rubber> [Vinyl content, aromatic styrene content] The sample was dissolved in deuterated chloroform.13 Measurements were performed using a C-NMR (JEOL ECZ500) under the following conditions. Resonance frequency: 125MHz Pulse width: 90° Repeat time: 8sec Total: 5120 times Temperature: room temperature Chemical shift reference: CDCl377.0ppm
[0161] [Viscosity at 25℃] The viscosity of the liquid rubber was measured using a Brookfield viscometer at a rotation speed of 10 rpm.
[0162] [Number average molecular weight (Mn) and weight average molecular weight (Mw)] The chromatogram was measured using GPC with three columns packed with polystyrene gel connected together, and the molecular weight (Mn, Mw) and molecular weight distribution (Mw / Mn) were calculated from a calibration curve using standard polystyrene. Tetrahydrofuran was used as the solvent.
[0163] <Rubber composition> [Appearance (dispersibility of cellulose nanofiber)] The rubber compositions obtained in Examples 1 to 5 and Comparative Examples 2 and 3 were observed under an optical microscope under the following conditions. 1 mg of the sample was sandwiched between two cover glasses and crushed and spread to a uniform thickness. The sample was placed on the stage of an Olympus BX51P polarizing microscope. An Olympus U-DICR differential interference prism was inserted and differential interference observation was performed. The dispersibility of the filler was evaluated according to the following criteria. A: Almost uniformly dispersed. B: Dispersed, but some aggregation is observed. C: Numerous aggregates are observed.
[0164] [Storage modulus] The storage modulus was measured by frequency dispersion measurement using parallel plates at a gap of 1 mm at 25°C and a strain of 0.002% using a HAAKE MARS40 rheometer manufactured by Thermo Fisher Scientific Co., Ltd. for the rubber compositions of Examples 1 to 5 and Comparative Examples 2 and 3, and the liquid rubber of Comparative Example 1. A high storage modulus indicates that the cellulose nanofibers are well dispersed in the rubber, and means that when the cellulose nanofibers are kneaded into rubber as a rubber master batch, they are well dispersed in the rubber, resulting in a rubber composition with excellent mechanical properties such as elastic modulus, storage modulus, and hardness.
[0165] <Dry powder> The dry powder was evaluated as follows using a powder tester (model: PT-X) manufactured by Hosokawa Micron Corporation.
[0166] [Loose bulk density] The dried material was poured into a stainless steel 100 mL (inner diameter 50.46 mm × depth 50 mm) bottomed cylindrical container at 10 g / min with a medicine spoon until it overflowed, and the dried material was leveled off and then weighed to the nearest 0.01 g. The number average value of the weight measured three times was divided by the internal volume of the bottomed cylindrical container to calculate the loose bulk density.
[0167] [Packed bulk density] A resin adapter (inner diameter 50.46 mm x length 40 mm) of sufficient capacity was attached to the top of the same bottomed cylindrical container used for the loose bulk density measurement so that it was in close contact with the container, and the dried material was poured into the container until it overflowed using the same procedure as for the measurement of the loose bulk density. The bottomed cylindrical container was then subjected to vibration with an amplitude of 1.5 mm and 50 Hz for 30 seconds using a motor with an eccentric weight attached to the rotating shaft while the adapter was still connected. The adapter was then removed, and the dried material was drained to the nearest 0.01 g, after which the weight was measured. The number average value of the weight measured three times was divided by the internal volume of the bottomed cylindrical container to calculate the packed bulk density.
[0168] <Cured rubber> The cured rubber products were evaluated as follows. (1) Tensile strength The evaluation was performed according to the tensile test method of JIS K-6251. (2) Storage modulus The storage modulus was evaluated at 50°C, a frequency of 10 Hz, and a strain of 3% using a torsion method using a TA Instruments viscoelasticity testing device ARES-G2. (3) Dispersibility of cellulose nanofibers The state of dispersion of the cellulose nanofibers in a 5 cm square area on the vulcanization press surface of the cured rubber was visually observed and evaluated according to the following criteria. A: No visible aggregates B: A small number of aggregates (1 to 10) are observed. C: Many aggregates (11 or more) were observed.
[0169] ≪Materials used≫ <Liquid rubber> Liquid rubber-1: butadiene-styrene random copolymer (RICON 184, available from Cray Valley), viscosity at 25°C 40,000 cP, number average molecular weight (Mn) 3,200, weight average molecular weight (Mw) 14,000, Mw / Mn 4.3, vinyl content 19 mol%, aromatic styrene content 8 mol% Liquid rubber-2: butadiene-styrene random copolymer (RICON 100, available from Cray Valley), viscosity at 25°C 75,000 cP, number average molecular weight (Mn) 2,100, weight average molecular weight (Mw) 4,500, Mw / Mn 2.1, vinyl content 42 mol%, aromatic styrene content 9 mol%
[0170] <Solution polymerized rubber> Rubber-1: Asaprene Y031 (available from Asahi Kasei Corporation)
[0171] <Cellulose nanofiber> CNF-1: Microfibrous cellulose (Cerish KY-100G, available from Daicel Miraize Co., Ltd.)
[0172] CNF-2: Microfibrillated cellulose 3 parts by mass of cotton linter pulp was immersed in 27 parts by mass of water and dispersed with a pulper. 30 parts by mass of the pulper-treated cotton linter pulp slurry (including 3 parts by mass of cotton linter pulp) was added to 170 parts by mass of water to disperse the mixture in water (solid content rate: 1.5% by mass), and the aqueous dispersion was beaten for 30 minutes using a SDR14 lab refiner (pressure type DISK type) manufactured by Aikawa Iron Works Co., Ltd. as a disc refiner device with a clearance between discs of 1 mm. Subsequently, thorough beating was performed under conditions in which the clearance was reduced to a level close to zero, to obtain a beaten aqueous dispersion (solid content concentration: 1.5% by mass). The obtained beaten aqueous dispersion was directly subjected to a high-pressure homogenizer (NSO15H manufactured by Niro Soavi Co., Ltd. (Italy)) for 10 times of refinement under an operating pressure of 100 MPa to obtain a fine cellulose fiber slurry (solid content concentration: 1.5% by mass). The mixture was then concentrated to a solid content of 10% by mass using a dehydrator to obtain a concentrated cake of CNF-2.
[0173] <Nonionic surfactant> Surfactant-1: Polyoxyethylene (2) monolauryl ether (Emulgen 102KG, available from Kao Corporation) (The number in parentheses indicates the repeat number of the oxyethylene chain.) Surfactant-2: Sorbitan monooleate (Rheodol SP-O10V, available from Kao Corporation) Surfactant-3: Polyoxyethylene (6) sorbitan monolaurate (Rheodol TW-L106, available from Kao Corporation) (The number in parentheses indicates the repeat number of the oxyethylene chain.) Surfactant-4: Ethylene glycol-propyne glycol copolymer (PEG-PPG) (Sannix GL-3000, available from Sanyo Chemical Industries, Ltd.)
[0174] <Thermoplastic elastomer> SEBS H1052: Product name "Tuftec H1052", manufactured by Asahi Kasei Corporation
[0175] <Silica> Silica-1: Precipitated silica (ULTRASIL 7000GR, available from Degussa)
[0176] <Silane coupling agent> Si75: Bis(3-(triethoxysilyl)propyl) disulfide (available from Evonik Japan Co., Ltd.)
[0177] <Oil> PF30: Mineral oil (available from JXTG Nippon Oil & Energy Corporation)
[0178] <Vulcanization aid> Zinc oxide: available from Fujifilm Wako Pure Chemical Industries, Ltd. Stearic acid: available from Fujifilm Wako Pure Chemical Industries, Ltd.
[0179] <Wax> Sunnock: Selected Special Wax (available from Ouchi Shinko Chemical Co., Ltd.)
[0180] <Anti-aging agent> Nocrac 6C: N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine (available from Ouchi Shinko Chemical Co., Ltd.)
[0181] <Vulcanization accelerator> Noccela CZ: N-cyclohexyl-2-benzothiazolyl sulfenamide (available from Ouchi Shinko Chemical Co., Ltd.) Noccelaer D: 1,3-diphenylguanidine (available from Ouchi Shinko Chemical Co., Ltd.)
[0182] <Preparation of rubber composition> <Example 1> Purified water was added to Celish KY100G (manufactured by Daicel FineChem Co., Ltd.) (aqueous dispersion of cellulose fiber) to prepare an aqueous dispersion with a final cellulose nanofiber content of 5% by mass. Liquid rubber-1 (RICON184) and surfactant-1 were added to this to prepare an aqueous dispersion with a final composition of 90% by mass of water, 5% by mass of cellulose fiber, 2.86% by mass of liquid rubber, and 2.14% by mass of surfactant. The aqueous dispersion was mixed for 5 minutes using a revolution mixer ARE-310 manufactured by Thinky Corporation to obtain a dispersion of a cellulose nanofiber composition. The obtained dispersion was dried at 80°C using SPH-201 manufactured by Espec Corporation to obtain a dried body. The obtained dried body was pulverized using a mini speed mill MS-05 manufactured by Labnect Co., Ltd., and then 20 parts by mass of the dried body was added to 80 parts by mass of liquid rubber-1 (RICON184), and mixed for 15 minutes using a revolution mixer ARE-310 manufactured by Thinky Corporation to obtain a rubber composition.
[0183] <Example 2> Purified water was added to Celish KY100G (manufactured by Daicel FineChem) (aqueous dispersion of cellulose fiber) to prepare an aqueous dispersion with a final cellulose nanofiber content of 5% by mass. Surfactant-1 was added to this to prepare an aqueous dispersion with a final composition of 92.86% by mass of water, 5% by mass of cellulose fiber, and 2.14% by mass of surfactant. The aqueous dispersion was mixed for 5 minutes using a centrifugal mixer ARE-310 manufactured by Thinky Corporation to obtain a dispersion of a cellulose nanofiber composition. The obtained dispersion was dried at 80°C using an SPH-201 manufactured by Espec Corporation to obtain a dried body. The obtained dried body was pulverized using a mini speed mill MS-05 manufactured by Labnect Co., Ltd., and then 14.29 parts by mass of the dried body was added to 85.71 parts by mass of liquid rubber-1 (RICON 184), and mixed for 15 minutes using a centrifugal mixer ARE-310 manufactured by Thinky Corporation to obtain a rubber composition.
[0184] <Example 3> A rubber composition was prepared under the same conditions as in Example 2, except that surfactant-1 was replaced with surfactant-2.
[0185] <Example 4> A rubber composition was prepared under the same conditions as in Example 2, except that surfactant-1 was replaced with surfactant-3.
[0186] <Example 5> A rubber composition was prepared under the same conditions as in Example 2, except that surfactant-1 was replaced with surfactant-4.
[0187] <Comparative Example 1> Liquid rubber-1 (RICON 184) was used as is.
[0188] <Comparative Example 2> 10 parts by mass of silica-1 was added to 90 parts by mass of liquid rubber-1 (RICON 184), and mixed for 15 minutes using a planetary centrifugal mixer ARE-310 manufactured by Thinky Corporation to obtain a rubber composition.
[0189] <Comparative Example 3> Purified water was added to Celish KY100G (manufactured by Daicel FineChem) (aqueous dispersion of cellulose fiber) to obtain an aqueous dispersion with a final cellulose nanofiber content of 5% by mass. Liquid rubber-1 (RICON184) was added to this to obtain an aqueous dispersion with a final composition of 92.86% by mass of water, 5% by mass of cellulose fiber, and 2.14% by mass of liquid rubber-1. The aqueous dispersion was mixed for 5 minutes using a centrifugal mixer ARE-310 manufactured by Thinky Corporation to obtain a dispersion of a cellulose nanofiber composition. The obtained dispersion was dried at 80°C using SPH-201 manufactured by Espec Corporation to obtain a dried body. The obtained dried body was pulverized using a mini speed mill MS-05 manufactured by Labnect Co., Ltd., and then 14.29 parts by mass of the pulverized dried body was added to 85.71 parts by mass of liquid rubber-1 (RICON 184), and mixed for 15 minutes using a centrifugal mixer ARE-310 manufactured by Thinky Corporation to obtain a rubber composition.
[0190] The results are shown in Table 1. In Examples 1 to 5, the cellulose nanofibers were well dispersed in the rubber, and the storage modulus at a frequency of 1 Hz was high. In Comparative Example 3, a large number of aggregates were contained in the rubber, and although the rubber was subjected to storage modulus measurement, a stable measured value could not be obtained.
[0191] [Table 1]
[0192] <Dispersion of rubber composition in thermoplastic elastomer> <Example 6> Purified water was added to Celish KY100G (manufactured by Daicel FineChem) (aqueous dispersion of cellulose fiber) to obtain an aqueous dispersion with a final cellulose nanofiber content of 5% by mass. Liquid rubber-2 (RICON100) and surfactant-1 were added to this to prepare an aqueous dispersion with a final composition of 90% by mass of water, 5% by mass of cellulose fiber, 7.86% by mass of liquid rubber, and 2.14% by mass of surfactant. The aqueous dispersion was mixed for 15 minutes using a centrifugal mixer ARE-310 manufactured by Thinky Corporation to obtain a dispersion of a cellulose nanofiber composition. The obtained dispersion was dried at 80°C using SPH-201 manufactured by Espec Corporation to obtain a rubber composition.
[0193] Next, 15 g of the rubber composition was added to 85 g of thermoplastic elastomer-1 (SEBS H1052) in a small mixer (Xplore) manufactured by Leo Labs, and the mixture was melt-mixed at 200°C for 5 minutes to obtain a rubber strand with dispersed cellulose nanofibers. The obtained rubber strand was hot-pressed at 200°C and 10 kN for 10 minutes to obtain a sheet. When the sheet was visually observed, no aggregates were observed.
[0194] <Comparative Example 4> Purified water was added to Celish KY100G (manufactured by Daicel FineChem) (aqueous dispersion of cellulose fibers) to obtain an aqueous dispersion with a final cellulose nanofiber content of 5% by mass. Surfactant-1 was added to this to prepare an aqueous dispersion with a final composition of 92.86% by mass of water, 5% by mass of cellulose fibers, and 2.14% by mass of surfactant. The aqueous dispersion was mixed for 15 minutes using a centrifugal mixer ARE-310 manufactured by Thinky Corporation to obtain a dispersion of a cellulose nanofiber composition. The obtained dispersion was dried at 80°C using an SPH-201 manufactured by Espec Corporation to obtain a cellulose nanofiber-containing composition.
[0195] Next, 7.1 g of the cellulose nanofiber-containing composition was added to 92.9 g of thermoplastic elastomer-1 (SEBS H1052) in a small mixer (Xplore) manufactured by Leo Labs, and the mixture was melt-mixed at 200°C for 5 minutes to obtain a rubber strand with dispersed cellulose nanofibers. The rubber strand was then heat-pressed at 200°C and 10 kN for 10 minutes to obtain a sheet. When the sheet was visually observed, numerous aggregates were confirmed.
[0196] <Production of cured rubber> <Example 7> Purified water was added to CNF-2 (aqueous dispersion of cellulose fibers) to prepare an aqueous dispersion with a final cellulose nanofiber content of 5% by mass. Liquid rubber-1 and surfactant-1 were added to this to prepare an aqueous dispersion with a final composition of 90% by mass of water, 5% by mass of cellulose fibers, 2.86% by mass of liquid rubber, and 2.14% by mass of surfactant. The aqueous dispersion was mixed for 5 minutes using a centrifugal mixer ARE-310 manufactured by Thinky Corporation to obtain a dispersion of a cellulose nanofiber composition. The obtained dispersion was dried at 80°C using SPH-201 manufactured by Espec Corporation to obtain a dried product. The obtained dried product was pulverized for 30 seconds using a mini speed mill MS-05 manufactured by LabNect Co., Ltd. to obtain a powder for producing a rubber cured product. The loose bulk density and packed bulk density of the obtained dry powder were measured by the above-mentioned method.
[0197] Next, a Toyo Seiki Laboplastomill was heated to 70°C, 100 parts by mass of rubber-1 (Asaprene Y031) was added and kneaded for 0.5 minutes, and 10 parts by mass of powder for producing rubber cured products, vulcanization aid (2.5 parts by mass of zinc oxide and 2 parts by mass of stearic acid), 1.5 parts by mass of wax, and 2 parts by mass of antioxidant were added and kneaded for 5.5 minutes to perform the first stage kneading. Next, the obtained first stage kneaded composition was added to the Laboplastomill heated to 70°C and kneaded for 0.5 minutes, and 1.7 parts by mass of sulfur and vulcanization accelerator (1.7 parts by mass of Noccela CZ and 2 parts by mass of Noccela D) were added according to the composition shown in Table 2 and kneaded for 2 minutes. The obtained second stage kneaded composition was vulcanized at 160°C for 20 minutes in a vulcanization press to obtain a rubber cured product.
[0198] <Example 8> A cured rubber product was obtained in the same manner as in Example 7, except that the dried product was pulverized using a Frevit Fredrive hammer mill instead of the LabNect Mini Speed Mill MS-05.
[0199] <Example 9> A cured rubber product was obtained in the same manner as in Example 7, except that the dried product was pulverized using a Flevit Fredrive conical screen mill instead of the LabNect Mini Speed Mill MS-05.
[0200] <Example 10> A cured rubber product was obtained in the same manner as in Example 7, except that the dried product was pulverized using a Flevit Fredrive pin mill instead of the LabNect Mini Speed Mill MS-05.
[0201] The dried material was crushed into powder, stained with OsO4 for 12 hours, mixed with epoxy resin, and left at room temperature for 48 hours to harden the epoxy resin. The hardened sample was cut with an ultramicrotome to prepare a smooth cross section, and Os plasma coating was performed for 1 second. The cellulose nanofibers were observed with a scanning electron microscope (Hitachi High-Technologies Corporation, SU8220) under the conditions of an accelerating voltage of 1.5 kV, WD of 3 mm, and an upper detector. The cellulose nanofibers were found to be coated with a rubber component (Figure 1). In Figure 1, the dark gray area is the cellulose nanofibers, the light gray area around the cellulose nanofibers is the first rubber component, and the black area is the epoxy resin. It was confirmed from Figure 1 that the cellulose nanofibers were coated with the first rubber component.
[0202] <Example 11> A cured rubber product was obtained in the same manner as in Example 7, except that surfactant-2 was used instead of surfactant-1 as the surfactant.
[0203] <Example 12> A cured rubber product was obtained in the same manner as in Example 7, except that the final composition of the aqueous dispersion was 92.86% by mass of water, 5% by mass of cellulose fiber, 1.43% by mass of liquid rubber, and 0.71% by mass of surfactant, instead of 90% by mass of water, 5% by mass of cellulose fiber, 2.86% by mass of liquid rubber, and 2.14% by mass of surfactant, and that 7.14 parts by mass of the powder for producing a cured rubber product was added instead of 10 parts by mass during the first stage of kneading.
[0204] <Example 13> A cured rubber product was obtained in the same manner as in Example 7, except that the final composition of the aqueous dispersion was 93.58 mass% water, 5 mass% cellulose fiber, 0.71 mass% liquid rubber, and 0.71 mass% surfactant, instead of 90 mass% water, 5 mass% cellulose fiber, 2.86 mass% liquid rubber, and 2.14 mass% surfactant, and that 6.42 mass parts of the powder for producing a cured rubber product were added instead of 10 mass parts during the first kneading stage.
[0205] <Example 14> A cured rubber material was obtained in the same manner as in Example 7, except that the final composition of the aqueous dispersion was 85% by mass of water, 5% by mass of cellulose fiber, 7.86% by mass of liquid rubber, and 2.14% by mass of surfactant, instead of 90% by mass of water, 5% by mass of cellulose fiber, 2.86% by mass of liquid rubber, and 2.14% by mass of surfactant, and that the dried product was pulverized by freeze-pulverization using a SPEX Freezer Mill 6875 instead of a LabNect Mini Speed Mill MS-05.
[0206] <Example 15> A Labo Plastomill manufactured by Toyo Seiki Co., Ltd. was heated to 70°C, 100 parts by mass of rubber-1 (Asaprene Y031) was added, and the mixture was kneaded for 0.5 minutes. 30 parts by mass of the powder for producing rubber cured products produced in Example 7 was added to the mixture, and the mixture was kneaded for 5.5 minutes to prepare a master batch. Then, the Labo Plastomill was heated to 70°C, 67 parts by mass of rubber-1 (Asaprene Y031) and 43 parts by mass of the master batch were added, and the mixture was kneaded for 0.5 minutes. A vulcanization aid (2.5 parts by mass of zinc oxide and 2 parts by mass of stearic acid), 1.5 parts by mass of wax, and 2 parts by mass of antioxidant were added, and the mixture was kneaded for 5.5 minutes to perform the first stage kneading. Next, 1.7 parts by mass of sulfur and vulcanization accelerator (1.7 parts by mass of Noccela CZ and 2 parts by mass of Noccela D) were added, and the mixture was kneaded for 2 minutes. The resulting second-stage mixed composition was vulcanized in a vulcanizing press at 160° C. for 20 minutes to obtain a cured rubber product.
[0207] <Reference example 5> A cured rubber product was obtained in the same manner as in Example 7, except that the dried product was dried under reduced pressure at 80°C using a Henschel mixer instead of drying at 80°C using an SPH-201 made by Espec Corporation, and the dried powder was used without being crushed.
[0208] <Reference example 6> A cured rubber product was obtained in the same manner as in Example 7, except that the crushing time of the dried product was changed from 30 seconds to 5 seconds.
[0209] <Reference example 7> Purified water was added to CNF-2 (aqueous dispersion of cellulose fibers) to prepare an aqueous dispersion with a final cellulose nanofiber content of 5% by mass. Liquid rubber-1 and surfactant-1 were added to this to prepare an aqueous dispersion with a final composition of 82.86% by mass of water, 5% by mass of cellulose fibers, 10% by mass of liquid rubber, and 2.14% by mass of surfactant. The aqueous dispersion was mixed for 5 minutes using a centrifugal mixer ARE-310 manufactured by Thinky Corporation to obtain a dispersion of a cellulose nanofiber composition. The obtained dispersion was dried at 80°C using SPH-201 manufactured by Espec Corporation to obtain a dried body. The obtained dried body was treated with a mini speed mill MS-05 manufactured by LabNect Co., Ltd. for 30 seconds. The dried body after the treatment was not in powder form, but in the form of fragments of a few mm in size.
[0210] Next, a Toyo Seiki Laboplastomill was heated to 70°C, 100 parts by mass of rubber-1 (Asaprene Y031) was added and kneaded for 0.5 minutes, and 17.14 parts by mass of powder for producing rubber cured products, vulcanization aid (2.5 parts by mass of zinc oxide and 2 parts by mass of stearic acid), 1.5 parts by mass of wax, and 2 parts by mass of antioxidant were added and kneaded for 5.5 minutes to perform the first stage kneading. Next, the obtained first stage kneaded composition was added to the Laboplastomill heated to 70°C and kneaded for 0.5 minutes, and 1.7 parts by mass of sulfur and vulcanization accelerator (1.7 parts by mass of Noccela CZ and 2 parts by mass of Noccela D) were added according to the composition shown in Table 2 and kneaded for 2 minutes. The obtained second stage kneaded composition was vulcanized at 160°C for 20 minutes in a vulcanization press to obtain a rubber cured product.
[0211] <Evaluation Results of Examples 7 to 15 and Reference Examples 5 to 7> The evaluation results of Examples 7 to 15 and Reference Examples 5 to 7 are shown in Table 2. In the Examples, the cellulose nanofibers were well dispersed in the rubber, and a significant improvement in the physical properties was confirmed.
[0212] [Table 2] [Industrial Applicability]
[0213] The rubber composition according to the present disclosure can be formed into molded articles having good physical properties, and therefore can be suitably used in a wide range of applications, such as industrial machine parts, general machine parts, automobile, railway, vehicle, ship, and aerospace related parts, electronic and electrical parts, building and civil engineering materials, daily necessities, sports and leisure goods, housing parts for wind power generation, containers and packaging parts, etc.
Claims
1. A powder of a rubber composition comprising cellulose nanofibers and a first rubber component which is a liquid rubber.
2. The powder according to claim 1 , wherein the cellulose nanofibers have no ionic groups.
3. 3. The powder according to claim 1 or 2, wherein the number average molecular weight of the liquid rubber is 1,000 to 80,000.
4. The powder according to any one of claims 1 to 3, wherein the ratio (Mw / Mn) of the number average molecular weight (Mn) to the weight average molecular weight (Mw) of the liquid rubber is 1.5 to 5.
5. The powder according to any one of claims 1 to 4, wherein the viscosity of the liquid rubber at 80°C is 1,000,000 mPa·s or less.
6. The powder according to any one of claims 1 to 5, wherein the viscosity of the liquid rubber at 25°C is 1,000,000 mPa·s or less.
7. The powder according to any one of claims 1 to 6, wherein the viscosity of the liquid rubber at 0°C is 1,000,000 mPa·s or less.
8. The powder according to any one of claims 1 to 7, wherein the liquid rubber comprises at least one selected from the group consisting of diene rubber, silicone rubber, urethane rubber, polysulfide rubber, and hydrogenated products thereof.
9. The powder according to any one of claims 1 to 8, wherein the degree of substitution of the cellulose nanofiber is 0.
10. The powder according to any one of claims 1 to 9, comprising 0.5% by mass to 10% by mass of the cellulose nanofibers.
11. A powder described in any one of claims 1 to 10, containing a surfactant.
12. The powder according to claim 11, comprising 10 parts by mass to 200 parts by mass of the surfactant per 100 parts by mass of the cellulose nanofibers.
13. 13. The powder according to claim 11 or 12, wherein the surfactant is a nonionic surfactant or a cationic surfactant.
14. 14. The powder according to claim 13, wherein the surfactant is a nonionic surfactant.
15. 15. The powder according to claim 14, wherein the nonionic surfactant is a compound having a hydrophilic group selected from the group consisting of a hydroxyl group, a carboxyl group, a sulfonic acid group, and an amino group, and a hydrocarbon group.
16. The nonionic surfactant is represented by the following general formula (1): R-(OCH) 2 CH 2 ) m -OH (1) [In the formula, R represents a monovalent aliphatic group having 6 to 30 carbon atoms, and m is a natural number smaller than the number of carbon atoms of R], and The following general formula (2): R 1 OCH 2 -(CHOH) 4 -CH 2 OR 2 (2) [In the formula, R 1 and R 2 each independently represents a hydrogen atom, an aliphatic group having 1 to 30 carbon atoms, -COR 3 {In the formula, R 3 represents an aliphatic group having 1 to 30 carbon atoms.}, or -(CH 2 CH 2 O) y -R 4 {In the formula, R 4 represents a hydrogen atom or an aliphatic group having 1 to 30 carbon atoms, and y is an integer of 1 to 30. The powder according to claim 14 or 15, which is one or more types selected from the group consisting of:
17. The powder according to any one of claims 1 to 16, wherein at least a portion of the surface of the cellulose nanofiber is covered with the first rubber component.
18. Compacted bulk density is 0.01 g / cm 3 ~0.30g / cm 3 The powder according to any one of claims 1 to 17,
19. A masterbatch, which is a mixture of the powder according to any one of claims 1 to 18 and a second rubber component.
20. A method for producing a masterbatch, comprising a step of kneading the powder according to any one of claims 1 to 18 with a second rubber component to obtain a masterbatch.
21. A rubber composite, which is a mixture of the powder according to any one of claims 1 to 18 or the masterbatch according to claim 19 and a third rubber component.
22. The rubber composite of claim 21 , wherein at least a portion of a surface of the cellulose nanofiber is covered with the first rubber component.
23. Kneading the powder according to any one of claims 1 to 18 with a third rubber component; or Forming a masterbatch by the method of claim 20, and then compounding the masterbatch with a third rubber component; A method for producing a rubber composite, comprising the step of obtaining a rubber composite by
24. The method of claim 23, wherein in the rubber composite, at least a portion of the surface of the cellulose nanofiber is covered by the first rubber component.
25. A cured rubber product, which is a cured product of the rubber composite according to claim 21 or 22.
26. Obtaining a rubber composite according to the method of claim 23 or 24, and A step of curing the rubber composite to obtain a cured rubber product. The method for producing a cured rubber product comprising the steps of:
27. A shoe outsole comprising the rubber vulcanized product of claim 25.
28. A tire comprising the rubber vulcanized product of claim 25.
29. A rubber vibration isolator comprising the cured rubber according to claim 25.
30. A power transmission belt comprising the rubber vulcanized product of claim 25.